Activation of Olfactory and Trigeminal Cortical Areas Following Stimulation of the Nasal Mucosa With Low Concentrations of S(-)-Nicotine Vapor-An fMRI Study on Chemosensory Perception - Albrecht, Jessica; Kopietz, Rainer; Linn, Jennifer; Sakar, Vehbi; Anzinger, Andrea; Schreder, Tatjana; Pollatos, Olga; Brueckmann, Hartmut; Kobal, Gerd; Wiesmann, Martin (Human Brain Mapping, 2009)
Applied to the nasal mucosa in low concentrations, nicotine vapor evokes odorous sensations (mediated by the olfactory system) whereas at higher concentrations nicotine vapor additionally produces burning and stinging sensations in the nose (mediated by the trigeminal system). The objective of this study was to determine whether intranasal stimulation with suprathreshold concentrations of S(-)-nicotine vapor causes brain activation in olfactory cortical areas or if trigeminal cortical areas are also activated. Individual olfactory detection thresholds for S(-)-nicotine were determined in 19 healthy occasional smokers using a computer-controlled air-dilution olfactometer. Functional magnetic resonance images were acquired using a 1.5T MR scanner with applications of nicotine in concentrations at or just above the individual's olfactory detection threshold. Subjects reliably perceived the stimuli as being odorous. Accordingly, activation of brain areas known to be involved in processing of olfactory stimuli was identified. Although most of the subjects never or only rarely observed a burning or painful sensation in the nose, brain areas associated with the processing of painful stimuli were activated in all subjects. This indicates that the olfactory and trigeminal systems are activated during perception of nicotine and it is not possible to completely separate olfactory from trigeminal effects by lowering the concentration of the applied nicotine. In conclusion, even at low concentrations that do not consistently lead to painful sensations, intranasally applied nicotine activates both the olfactory and the trigeminal system. Hum Brain Mapp 30:699-710, 2009. (c) 2008 Wiley-Liss, Inc.
Keywords: olfaction; odor; olfactometer; threshold; olfactory; trigeminal; nociception; fMRI

Altered likelihood of brain activation in attention and working memory networks in patients with multiple sclerosis: An ALE meta-analysis - Kollndorfer, Kathrin; Krajnik, J.; Woitek, Ramona; Freiherr, Jessica; Prayer, D.; Schoepf, V. (Neuroscience and Biobehavioral Reviews, 2013)
Multiple sclerosis (MS) is a chronic neurological disease, frequently affecting attention and working memory functions. Functional imaging studies investigating those functions in MS patients are hard to compare, as they include heterogeneous patient groups and use different paradigms for cognitive testing. The aim of this study was to investigate alterations in neuronal activation between MS patients and healthy controls performing attention and working memory tasks. Two meta-analyses of previously published fMRI studies investigating attention and working memory were conducted for MS patients and healthy controls, respectively. Resulting maps were contrasted to compare brain activation in patients and healthy controls. Significantly increased brain activation in the inferior parietal lobule and the dorsolateral prefrontal cortex was detected for healthy controls. In contrast, higher neuronal activation in MS patients was obtained in the left ventrolateral prefrontal cortex and the right premotor area. With this meta-analytic approach previous results of investigations examining cognitive function using fMRI are summarized and compared. Therefore a more general view on cognitive dysfunction in this heterogeneous disease is enabled. (C) 2013 The Authors. Published by Elsevier Ltd. All rights reserved.
Keywords: Multiple sclerosis; Brain imaging; Working memory; Attention; Activation likelihood estimation; VLPFC; DLPFC; n-Back; PASAT; PVSAT

A masked aversive odor cannot be discriminated from the masking odor but can be identified through odor quality ratings and neural activation patterns - Rodriguez-Raecke, Rea; Loos, Helene; Sijben, Rik; Singer, Marco; Beauchamp, Jonathan; Büttner, Andrea; Freiherr, Jessica (Frontiers in Neuroscience, 2019)
Odor masking is a very prominent problem in our daily routines, mainly concerning unpleasant sweat or toilet odors. In the current study we explored the effectiveness of odor masking both on a behavioral and neuronal level. By definition, participants cannot differentiate a fully masked unpleasant odor from the pleasant pure odor used as a masking agent on a behavioral level. We hypothesized, however, that one can still discriminate between a fully masked odor mixture and the pure masking odor on a neuronal level and that, using a reinforcing feedback paradigm, participants could be trained to perceive this difference. A pleasant, lemon-like odor (citral) and a mixture of citral and minor amounts of an unpleasant, goat-like odor (caproic acid) were presented to participants repeatedly using a computer-controlled olfactometer and participants had to decide whether two presented stimuli were the same or different. Accuracy of this task was incentivized with a possible monetary reward. Functional imaging was used throughout the task to investigate central processing of the two stimuli. The participants rated both stimuli as isopleasant and isointense, indicating that the unpleasant odor was fully masked by the pleasant odor. The isolated caproic acid component of the mixture was rated less pleasant than the pleasant odor in a prior experimental session. Although the masked and pure stimuli were not discriminated in the forced-choice task, quality ratings on a dimensional scale differed. Further, we observed an increased activation of the insula and ventral striatum/putamen for the pure in contrast to the fully masked odor, hence revealing a difference in neuronal processing. Our hypothesis that perceptual discrimination and neuronal processing can be enhanced using a reinforcing feedback paradigm is not supported by our data.
CRIS-Team Scopus Importer:2019-11-26
Keywords: FMRI; Odor masking; Odor mixture; Piriform cortex; Ventral striatum

A Multisensory Deficit in the Perception of Pleasantness in Parkinson's Disease. - Utz, Kathrin; Martini, Max; Mrochen, Anne; Lambrecht, Vera; Süß, Patrick; Renner, Bertold; Freiherr, Jessica; Schenk, Thomas; Winkler, Jürgen; Marxreiter, Franz (Journal of Parkinson's Disease, 2021)
BACKGROUND: There is growing interest in non-motor symptoms in Parkinson's disease (PD), due to the impact on quality of life. Anhedonia, the inability to experience joy and lust, has a prevalence of up to 46% in PD. The perception of pleasantness of an odor is reduced in anhedonia without PD. We previously showed a reduced hedonic olfactory perception in PD, i.e., patients evaluated odors as less pleasant or unpleasant compared to controls. This deficit correlated with anhedonia. OBJECTIVE: We aimed to confirm these findings. Moreover, we hypothesized that the perception of pleasantness in PD is affected on a multisensory level and correlates with anhedonia. Therefore, we assessed olfactory, visual and acoustic evaluation of pleasantness in PD and healthy individuals. METHODS: Participants had to rate the pleasantness of 22 odors, pictures, and sounds on a nine-point Likert scale. Depression, anhedonia, and apathy were assessed by means of questionnaires. Results of the pleasantness-rating were compared between groups and correlated to scores of the questionnaires. RESULTS: In particular pleasant and unpleasant stimuli across all three modalities are perceived less intense in PD, suggesting that a reduced range of perception of pleasantness is a multisensory phenomenon. However, only a reduction of visual hedonic perception correlated with anhedonia in PD. A correlation of reduced perception of pleasantness with apathy or depression was not present. CONCLUSION: We provide evidence for a multisensory deficit in the perception of pleasantness. Further studies should delineate the underlying neural circuity and the diagnostic value to detect neuropsychiatric symptoms in PD.
EVALuna2:470167

A Multisensory Deficit in the Perception of Pleasantness in Parkinson's Disease - Utz, Kathrin; Martini, Max; Mrochen, Anne; Lambrecht, Vera; Süß, Patrick; Renner, Bertold; Freiherr, Jessica; Schenk, Thomas; Winkler, Jürgen; Marxreiter, Franz (Journal of Parkinson's Disease, 2021)
Background: There is growing interest in non-motor symptoms in Parkinson's disease (PD), due to the impact on quality of life. Anhedonia, the inability to experience joy and lust, has a prevalence of up to 46% in PD. The perception of pleasantness of an odor is reduced in anhedonia without PD. We previously showed a reduced hedonic olfactory perception in PD, i.e., patients evaluated odors as less pleasant or unpleasant compared to controls. This deficit correlated with anhedonia. Objective: We aimed to confirm these findings. Moreover, we hypothesized that the perception of pleasantness in PD is affected on a multisensory level and correlates with anhedonia. Therefore, we assessed olfactory, visual and acoustic evaluation of pleasantness in PD and healthy individuals. Methods: Participants had to rate the pleasantness of 22 odors, pictures, and sounds on a nine-point Likert scale. Depression, anhedonia, and apathy were assessed by means of questionnaires. Results of the pleasantness-rating were compared between groups and correlated to scores of the questionnaires. Results: In particular pleasant and unpleasant stimuli across all three modalities are perceived less intense in PD, suggesting that a reduced range of perception of pleasantness is a multisensory phenomenon. However, only a reduction of visual hedonic perception correlated with anhedonia in PD. A correlation of reduced perception of pleasantness with apathy or depression was not present. Conclusion: We provide evidence for a multisensory deficit in the perception of pleasantness. Further studies should delineate the underlying neural circuity and the diagnostic value to detect neuropsychiatric symptoms in PD.
CRIS-Team Scopus Importer:2021-10-29
Keywords: affective pictures; anhedonia; apathy; depression; hyposmia; non-motor symptoms; Parkinson's disease; Sniffin' Sticks

A Phenotyping Platform to Characterize Healthy Individuals Across Four Stages of Life - The Enable Study - Brandl, Beate; Skurk, Thomas; Rennekamp, Rachel; Hannink, Anne; Kiesswetter, Eva; Freiherr, Jessica; Ihsen, Susanne; Roosen, Jutta; Klingenspor, Martin; Haller, Dirk; Krautwurst, Dietmar; Hofmann, Thomas; et al. (Frontiers in Nutrition, 2020)
Introduction: Nutritional habits and requirements are changing over the lifespan, but the dynamics of nutritional issues and the diet-health relationship in the major stages of the human life cycle are not sufficiently understood. A human phenotyping research platform for nutrition studies was established to recruit and phenotype selected population groups across different stages of life. The project is the backbone of the highly interdisciplinary enable competence cluster of nutrition research aiming to identify dietary determinants of a healthy life throughout the lifespan and to develop healthier and tasty convenience foods with high consumer acceptance. Methods: The phenotyping program included anthropometry, body composition analysis, assessment of energy metabolism, health and functional status, multisensory perception, metabolic phenotyping, lifestyle, sociodemography, chronobiology, and assessment of dietary intake including food preferences and aversions. Results: In total, 503 healthy volunteers at four defined phases of life including 3–5-year old children (n = 44), young adults aged 18–25 years (n = 94), adults aged 40–65 years (“middle agers,” n = 205), and older adults aged 75–85 years (n = 160) were recruited and comprehensively phenotyped. Plasma, serum, buffy coat, urine, feces and saliva samples were collected and stored at −80°C. Significant differences in anthropometric and metabolic parameters between the four groups were found. A major finding was the decrease in fat-free mass and the concomitant increase in % body fat in both sexes across the adult lifespan. Conclusions: The dataset will provide novel information on differences in diet-related parameters over the lifespan and is available for targeted analyses. We expect that this novel platform approach will have implications for the development of innovative food products tailored to promote healthy eating throughout life. Trial registration: DRKS, DRKS00009797. Registered on 20 January 2016, https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&_ID=DRKS00009797.
CRIS-Team Scopus Importer:2020-11-20
Keywords: biosamples; cohort; enable-cluster; metabolic phenotyping; nutrition

Application of Deep Learning on Foci of Neural Activity Makes It Possible to Identify Crucial Brain Areas for the Classification of Aversive and Hedonic Neural Odor Processing - Lermer, Raphael; Torske, Alyssa; Bauer, Thilo; Freiherr, Jessica (CHEMICAL SENSES, 2021)
CRIS-Team WoS Importer:2021-12-24

Audio-visual and olfactory-visual integration in healthy participants and subjects with autism spectrum disorder - Stickel, Susanne; Weismann, Pauline; Kellermann, Thilo; Regenbogen, Christina; Habel, Ute; Freiherr, Jessica; Chechko, Natalya (Human Brain Mapping, 2019)
The human capacity to integrate sensory signals has been investigated with respect to different sensory modalities. A common denominator of the neural network underlying the integration of sensory clues has yet to be identified. Additionally, brain imaging data from patients with autism spectrum disorder (ASD) do not cover disparities in neuronal sensory processing. In this fMRI study, we compared the underlying neural networks of both olfactory–visual and auditory–visual integration in patients with ASD and a group of matched healthy participants. The aim was to disentangle sensory-specific networks so as to derive a potential (amodal) common source of multisensory integration (MSI) and to investigate differences in brain networks with sensory processing in individuals with ASD. In both groups, similar neural networks were found to be involved in the olfactory–visual and auditory–visual integration processes, including the primary visual cortex, the inferior parietal sulcus (IPS), and the medial and inferior frontal cortices. Amygdala activation was observed specifically during olfactory–visual integration, with superior temporal activation having been seen during auditory–visual integration. A dynamic causal modeling analysis revealed a nonlinear top-down IPS modulation of the connection between the respective primary sensory regions in both experimental conditions and in both groups. Thus, we demonstrate that MSI has shared neural sources across olfactory–visual and audio–visual stimulation in patients and controls. The enhanced recruitment of the IPS to modulate changes between areas is relevant to sensory perception. Our results also indicate that, with respect to MSI processing, adults with ASD do not significantly differ from their healthy counterparts.
CRIS-Team Scopus Importer:2019-08-02
Keywords: auditory–visual integration; autism spectrum disorder; dynamic causal modeling; fMRI; multisensory integration; olfactory–visual integration

Bayesian informed evidence against modulation of androstadienone-effects by genotypic receptor variants and participant sex: A study assessing Stroop interference control, mood and olfaction - Hornung, Jonas; Noack, Hannes; Thomas, Mara; Farger, Gisbert; Nieratschker, Vanessa; Freiherr, Jessica; Derntl, Birgit (Hormones and Behavior, 2018)
The androgen derivative androstadienone (AND) is present in human sweat and may act as human chemosignal. Though effects of AND have been reported with respect to emotional and cognitive processes, results have been highly inconsistent. For this reason, it is likely that AND-action is dependent on modulatory factors. Here we wanted to specifically investigate the impact of genotypic variations of the AND-receptor OR7D4, as well as the influence of participant sex and concomitant hormonal fluctuations on AND-action during emotional interference processing, olfactory performance and mood assessments.To this end 80 healthy individuals (women taking oral contraceptives; naturally cycling women measured during the luteal phase and men) were tested twice on two consecutive days (AND vs. placebo exposure) with an emotional Stroop task. Also, olfactory performance and mood was assessed. Participants provided saliva samples to measure testosterone, progesterone and estradiol and a blood sample to assess genotypic variations of the AND-receptor OR7D4.We found a small task-dependent reduction of overall error rates under AND but no modulation of effects by genetic variation or group (female OC, female NC, male) with respect to olfactory performance and mood. Additional analyses with help of Bayesian statistics gave strong evidence in favor of specific null hypotheses suggesting that the action of AND was not modulated by either genotypic variations or sex of participants with respect to interference control (bias indices), olfactory self-reports and mood parameters.Additional effects of AND in connection with hormonal fluctuations are reported.
Keywords: Androstadienone; Pheromones; Emotional Stroop task; OR7D4; Sex differences; Oral contraceptives; Menstrual cycle; Sex hormones; Bayesian statistics

Beyond Distracted Eating: Cognitive Distraction Downregulates Odor Pleasantness and Interacts with Weight Status - Ruda, Iryna; Chellapandian, Deepak Charles; Rott, Marlene; Scheid, Selina; Freiherr, Jessica (Nutrients, 2024)
Considering the widespread issue of distracted eating, our study investigates how cognitive distraction influences the sensory perception of food-related odors among individuals with varying weight statuses. We conducted an exploratory, randomized, and cross-sectional experimental study, using the Tetris game to simulate real-life cognitive distraction, incorporating two distraction levels (low and high) and presenting five distinct odors. A total of 59 participants, categorized into a lean (n = 30) and overweight/obese group (n = 29) based on their body mass index (BMI), received odor stimuli while playing Tetris at low and high difficulty, corresponding to low and high distraction levels, respectively. Participants subsequently rated odor intensity and pleasantness under the two cognitive distraction conditions. Respiratory movements were monitored to ensure accurate olfactory stimulation. Our findings revealed no significant difference in odor intensity ratings across distraction levels (p = 0.903). However, there was a significant reduction in odor pleasantness under high cognitive distraction (p = 0.007), more pronounced in lean participants compared to those with an overweight status (p = 0.035). Additionally, an interaction between gender and cognitive distraction effects was observed in odor pleasantness perception. The differential effects of distraction across weight-status groups and genders are discussed in the context of hedonic motivation and compensatory mechanisms. This study sheds light onto the sensory mechanisms underlying distracted eating and could inform more personalized strategies for promoting healthier eating habits in a world dominated by distractions.
CRIS-Team Scopus Importer:2024-09-20
Keywords: distracted eating; hedonic eating; obesity; odor intensity; odor perception; odor pleasantness

Bloody olfaction? Confounding associations of sex and age on the influence of blood parameters and body weight on odor identification performance in healthy adults - Schicker, Doris; Karacan, Brid; Brandl, Beate; Skurk, Thomas; Volkert, Dorothee; Hauner, Hans; Freiherr, Jessica (Physiology & behavior, 2022)
Olfactory function and nutrition are closely related and may influence each other via metabolic parameters. However, the relationship between nutritional blood parameters and olfactory performance is still unclear. Inconclusive findings exist for specific blood parameters. In this extensive analysis, we examined the relationship between olfactory performance, measured with MONEX-40, as well as intensity and pleasantness ratings with 38 metabolic blood parameters, age, sex, and the anthropometric measurements body mass index (BMI) and body fat percentage (BFP). Therefore, we included data of 418 healthy, well-phenotyped Caucasians of the Enable cohort. We replicated age-dependent olfactory identification scores (p < 0.001) and found slight evidence for a body fat dependence measured with BFP (BF10 = 10.466). We further identified a sex difference only in middle-aged adults (p < 0.001) that could be explained by environmental factors. Several blood parameters correlated significantly with the MONEX-40 score (p < 0.05 – p < 0.001). However, these effects diminished after adjusting for sex and age (p > 0.9) that were identified as confounders. The same applies for BFP. In addition, no parameters were identified to correlate significantly with perceived olfactory intensity or pleasantness score if controlled for sex and age (p > 0.08). Our results suggest that metabolic blood parameters are not related to olfactory identification performance in a relevant manner and highlight the importance of controlling for sex and age in chemosensory research.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Age; Blood parameter; Body weight; Nutrition; Olfaction; Sex

Brain activations during pain: a neuroimaging meta-analysis of patients with pain and healthy controls - Jensen, Karin B.; Regenbogen, Christina; Ohse, Margarete C.; Frasnelli, Johannes; Freiherr, Jessica; Lundstrom, Johan N. (Pain, 2016)
In response to recent publications from pain neuroimaging experiments, there has been a debate about the existence of a primary pain region in the brain. Yet, there are few meta-analyses providing assessments of the minimum cerebral denominators of pain. Here, we used a statistical meta-analysis method, called activation likelihood estimation, to define (1) core brain regions activated by pain per se, irrelevant of pain modality, paradigm, or participants and (2) activation likelihood estimation commonalities and differences between patients with chronic pain and healthy individuals. A subtraction analysis of 138 independent data sets revealed that the minimum denominator for activation across pain modalities and paradigms included the right insula, secondary sensory cortex, and right anterior cingulate cortex (ACC). Common activations for healthy subjects and patients with pain alike included the thalamus, ACC, insula, and cerebellum. A comparative analysis revealed that healthy individuals were more likely to activate the cingulum, thalamus, and insula. Our results point toward the central role of the insular cortex and ACC in pain processing, irrelevant of modality, body part, or clinical experience; thus, furthering the importance of ACC and insular activation as key regions for the human experience of pain.
Keywords: Pain; Meta-analysis; Chronic pain; Neuroimaging; Thalamus; Cingulate cortex

Central Insulin Administration Improves Odor-Cued Reactivation of Spatial Memory in Young Men - Bruenner, Yvonne F.; Kofoet, Anja; Benedict, Christian; Freiherr, Jessica (Journal of Clinical Endocrinology and Metabolism, 2015)
Context: Insulin receptors are ubiquitously found in the human brain, comprising the olfactory bulb, essential for odor processing, and the hippocampus, important for spatial memory processing.Objective: The present study aimed at examining if intranasal insulin, which is known to transiently increase brain insulin levels in humans, would improve odor-cued reactivation of spatial memory in young men.Design: We applied a double-blind, placebo-controlled, counterbalanced within-subject design. Setting: The study was conducted at the research unit of a university hospital.Interventions/Participants/Main Outcome Measures: Following intranasal administration of either insulin (40 I.U.) or placebo, male subjects (n = 18) were exposed to eight odors. During each odor exposure, a green-colored field was presented on a 17-in. computer screen. During immediate recall (comprising 3 runs), the participants were re-exposed to each odor cue, and were asked to select the corresponding field (with visual feedback after each response). The delayed recall was scheduled similar to 10 min later (without feedback). To test if insulin's putative effect on odor-place memory would be domain-specific, participants also performed a separate place and odor recognition task.Results: Intranasal insulin improved the delayed but not immediate odor-cued recall of spatial memory. This effect was independent of odor type and in the absence of systemic side effects (eg, fasting plasma glucose levels remained unaltered). Place and odor recognition were unaffected by the insulin treatment.Conclusions: These findings suggest that acute intranasal insulin improves odor-cued reactivation of spatial memory in young men.

Chemosensory Communication of Gender Information: Masculinity Bias in Body Odor Perception and Femininity Bias Introduced by Chemosignals During Social Perception - Mutic, Smiljana; Moellers, Eileen M.; Wiesmann, Martin; Freiherr, Jessica (Frontiers in Psychology, 2016)
Human body odor is a source of important social information. In this study, we explore whether the sex of an individual can be established based on smelling axillary odor and whether exposure to male and female odors biases chemosensory and social perception. In a double-blind, pseudo-randomized application, 31 healthy normosmic heterosexual male and female raters were exposed to male and female chemosignals (odor samples of 27 heterosexual donors collected during a cardio workout) and a no odor sample. Recipients rated chemosensory samples on a masculinity-femininity scale and provided intensity, familiarity and pleasantness ratings. Additionally, the modulation of social perception (gender neutral faces and personality attributes) and affective introspection (mood) by male and female chemosignals was assessed. Male and female axillary odors were rated as rather masculine, regardless of the sex of the donor. As opposed to the masculinity bias in the odor perception, a femininity bias modulating social perception appeared. A facilitated femininity detection in gender neutral faces and personality attributes in male and female chemosignals appeared. No chemosensory effect on mood of the rater was observed. The results are discussed with regards to the use of male and female chemosignals in affective and social communication.
Keywords: sex; sexual dimorphism; sex recognition; mood; body odor; olfaction

Chemosensory danger detection in the human brain: Body odor communicating aggression modulates limbic system activation - Mutic, Smiljana; Briinner, Yvonne F.; Rodriguez-Raecke, Rea; Wiesmann, Martin; Freiherr, Jessica (Neuropsychologia, 2017)
Although the sense of smell is involved in numerous survival functions, the processing of body odor emitted by dangerous individuals is far from understood. The aim of the study was to explore how human fight chemosignals communicating aggression can alter brain activation related to an attentional bias and danger detection. While the anterior cingulate cortex (ACC) was seen involved in processing threat-related emotional information, danger detection and error evaluation, it still remains unknown whether human chemosignals communicating aggression can potentially modulate this activation. In the fMRI experiment, healthy male and female normosmic odor recipients (n=18) completed a higher-order processing task (emotional Stroop task with the word categories anger, anxiety, happiness and neutral) while exposed to aggression and exercise chemosignals (collected from a different group of healthy male donors; n=16). Our results provide first evidence that aggression chemosignals induce a time-sensitive attentional bias in chemosensory danger detection and modulate limbic system activation. During exposure to aggression chemosignals compared to exercise chemosignals, functional imaging data indicates an enhancement of thalamus, hypothalamus and insula activation (p <.05, FWE-corrected). Together with the thalamus, the ACC was seen activated in response to threat-related words (p <.001). Chemosensory priming and habituation to body odor signals are discussed.
Keywords: Chemosensation; Chemosignal; Olfaction; Anger; Threat

Chemosensory danger detection in the human brain - Freiherr, Jessica (Chemical Senses, 2019)

Cognitive Load Alters Neuronal Processing of Food Odors - Hoffmann-Hensel, Sonja Maria; Sijben, Rik; Rodriguez-Raecke, Rea; Freiherr, Jessica (Chemical Senses, 2017)
Obesity is a major health concern in modern societies. Although decreased physical activity and enhanced intake of high-caloric foods are important risk factors for developing obesity, human behavior during eating also plays a role. Previous studies have shown that distraction while eating increases food intake and leads to impaired processing of food stimuli. As olfaction is the most important sense involved in flavor perception, we used functional magnetic resonance imaging techniques to investigate the influence of cognitive memory load on olfactory perception and processing. Low-and high-caloric food odors were presented in combination with either low or high cognitive loads utilizing a memory task. The efficacy of the memory task was verified by a decrease in participant recall accuracy and an increase in skin conductance response during high cognitive load. Our behavioral data reveal a diminished perceived intensity for low-but not high-caloric food odors during high cognitive load. For low-caloric food odors, bilateral orbitofrontal (OFC) and piriform cortices (pirC) showed significantly lower activity during high compared with low cognitive load. For high-caloric food odors, a similar effect was established in pirC, but not in OFC. Insula activity correlates with higher intensity ratings found during the low cognitive load condition. We conclude lower activity in pirC and OFC to be responsible for diminished intensity perception, comparable to results in olfactory impaired patients and elderly. Further studies should investigate the influence of olfactory/gustatory intensities on food choices under distraction with special regards to low-caloric food.
Keywords: fMRI; obesity; olfaction; piriform cortex; skin conductance response

Cognitive load alters neuronal processing of food odors - Hoffmann-Hensel, Sonja M.; Sijben, Rik; Rodriguez-Raecke, Rea; Freiherr, Jessica (Chemical Senses, 2018)

Combining input from multiple sensory systems: Insights from behavioral and functional neuroimaging studies employing multisensory stimulation - Freiherr, Jessica; Lundstrom, Johan (ACS National Meeting Book of Abstracts, 2013)

Consistent social odor representation across 7 languages: the Social Odor Scale translation and validation - Cecchetto, Cinzia; Leleu, Arnaud; Calce, Roberta P.; Arnhardt, Sally; Parma, Valentina; de Groot, Jasper H.B.; Freiherr, Jessica; Gentili, Claudio; Zou, Laiquan; Thunell, Evelina; Fischmeister, Florian Ph S.; Rekow, Diane; et al. (Chemical Senses, 2024)
The Social Odor Scale (SOS) is a 12-item questionnaire initially developed and validated in Italian and German to investigate self-reported awareness of social odors, which are odors emanating from the human body that convey diverse information and evoke various emotional responses. The scale includes a total score and 3 subscales representing social odors in the respective categories: romantic partner, familiar, and strangers. Here, we aimed to (i) replicate the validation of the Italian and German versions of the SOS, (ii) translate and validate the SOS into multiple additional languages (French, English, Dutch, Swedish, Chinese), and (iii) explore whether the factor structure of each translated version aligns with the original versions. Confirmatory Factor Analysis (CFA) supported the scale's structure, yielding a good fit across all languages. Notable differences in SOS mean scores were observed among the different languages: Swedish participants exhibited lower social odor awareness compared to the other groups, whereas Chinese participants reported higher social odor awareness compared to Dutch and Swedish participants. Furthermore, SOS scores correlated with respondents' geographical location, with higher (i.e. northern) latitudes linked to lower social odor awareness. These results corroborate the SOS as a valid and reliable instrument, especially for the SOS total score and the Familiar and Partner factors, emphasizing the influence of individual and geographic factors on social odor awareness.
CRIS-Team Scopus Importer:2024-10-18
Keywords: body odors; culture; odor awareness; olfaction; social odors

Correction to: Out of the woods: psychophysiological investigations on wood odors to estimate their suitability as ambient scents (Wood Science and Technology, (2020), 54, 5, (1385-1400), 10.1007/s00226-020-01216-y) - Schreiner, Linda; Karacan, Brid; Blankenagel, Sonja; Packhaeuser, Kai; Freiherr, Jessica; Loos, Helene (Wood Science and Technology, 2021)
The article [Out of the woods: psychophysiological investigations on wood odors to estimate their suitability as ambient scents], written by [Linda Schreiner, Brid Karacan, Sonja Blankenagel, Kai Packhaeuser, Jessica Freiherr and Helene M. Loos], was originally published Online First without Open Access. After publication in volume [54], issue [5], page [1385–1400] the author decided to opt for Open Choice and to make the article an Open Access publication. Therefore, the copyright of the article has been changed to © [The Author(s)] [2021] and this article is licensed under a Creative Commons Attribution 4.0 International License, which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The images or other third party material in this article are included in the article’s Creative Commons licence, unless indicated otherwise in a credit line to the material. If material is not included in the article’s Creative Commons licence and your intended use is not permitted by statutory regulation or exceeds the permitted use, you will need to obtain permission directly from the copyright holder. To view a copy of this licence, visit http://creativecommons.org/licenses/by/4.0/. The original article has been corrected.
CRIS-Team Scopus Importer:2021-12-17

Corrigendum to: More Than Smell-COVID-19 Is Associated With Severe Impairment of Smell, Taste, and Chemesthesis. - Parma, Valentina; Ohla, Kathrin; Veldhuizen, Maria G.; Niv, Masha Y.; Kelly, Christine E.; Bakke, Alyssa J.; Cooper, Keiland W.; Bouysset, Cedric; Pirastu, Nicola; Dibattista, Michele; Kaur, Rishemjit; Liuzza, Marco Tullio; et al. (Chemical Senses, 2021)
EVALuna2:505077

Deep Learning-Based Detection of Intracranial Aneurysms in 3D TOF-MRA - Sichtermann, Thorsten; Faron, Anton; Sijben, R.; Teichert, Nikolas; Freiherr, Jessica; Wiesmann, Martin (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: The rupture of an intracranial aneurysm is a serious incident, causing subarachnoid hemorrhage associated with high fatality and morbidity rates. Because the demand for radiologic examinations is steadily growing, physician fatigue due to an increased workload is a real concern and may lead to mistaken diagnoses of potentially relevant findings. Our aim was to develop a sufficient system for automated detection of intracranial aneurysms.MATERIALS AND METHODS: In a retrospective study, we established a system for the detection of intracranial aneurysms from 3D TOF-MRA data. The system is based on an open-source neural network, originally developed for segmentation of anatomic structures in medical images. Eighty-five datasets of patients with a total of 115 intracranial aneurysms were used to train the system and evaluate its performance. Manual annotation of aneurysms based on radiologic reports and critical revision of image data served as the reference standard. Sensitivity, false-positives per case, and positive predictive value were determined for different pipelines with modified pre- and postprocessing.RESULTS: The highest overall sensitivity of our system for the detection of intracranial aneurysms was 90% with a sensitivity of 96% for aneurysms with a diameter of 3-7mmand 100% for aneurysms of >7 mm. The best location-dependent performance was in the posterior circulation. Pre- and postprocessing sufficiently reduced the number of false-positives.CONCLUSIONS: Our system, based on a deep learning convolutional network, can detect intracranial aneurysms with a high sensitivity from 3D TOF-MRA data.

Depicting the Inner and Outer Nose: The Representation of the Nose and the Nasal Mucosa on the Human Primary Somatosensory Cortex (SI) - Gastl, Mareike; Bruenner, Yvonne F.; Wiesmann, Martin; Freiherr, Jessica (Human Brain Mapping, 2014)
The nose is important not only for breathing, filtering air, and perceiving olfactory stimuli. Although the face and hands have been mapped, the representation of the internal and external surface of the nose on the primary somatosensory cortex (SI) is still poorly understood. To fill this gap functional magnetic resonance imaging (fMRI) was used to localize the nose and the nasal mucosa in the Brodman areas (BAs) 3b, 1, and 2 of the human postcentral gyrus (PG). Tactile stimulation during fMRI was applied via a customized pneumatically driven device to six stimulation sites: the alar wing of the nose, the lateral nasal mucosa, and the hand (serving as a reference area) on the left and right side of the body. Individual representations could be discriminated for the left and right hand, for the left nasal mucosa and left alar wing of the nose in BA 3b and BA 1 by comparing mean activation maxima and Euclidean distances. Right-sided nasal conditions and conditions in BA 2 could further be separated by different Euclidean distances. Regarding the alar wing of the nose, the results concurred with the classic sensory homunculus proposed by Penfield and colleagues. The nasal mucosa was not only determined an individual and bilateral representation, its position on the somatosensory cortex is also situated closer to the caudal end of the PG compared to that of the alar wing of the nose and the hand. As SI is commonly activated during the perception of odors, these findings underscore the importance of the knowledge of the representation of the nasal mucosa on the primary somatosensory cortex, especially for interpretation of results of functional imaging studies about the sense of smell. (C) 2014 Wiley Periodicals, Inc.
Keywords: primary somatosensory cortex (SI); nasal mucosa; fMRI; somatotopy; somatosensory stimulation; homunculus; olfaction

Development and validation of a food-associated olfactory test (FAOT) - Denzer-Lippmann, Melanie; Beauchamp, Jonathan; Freiherr, Jessica; Thürauf, Norbert; Kornhuber, Johannes; Büttner, Andrea (Chemical Senses, 2017)
Olfactory tests are an important tool in human nutritional research for studying food preferences, yet comprehensive tests dedicated solely to food odors are currently lacking. Therefore, within this study, an innovative food-associated olfactory test (FAOT) system was developed. The FAOT comprises 16 odorant pens that contain representative food odors relating to different macronutrient classes. The test underwent a sensory validation based on identification rate, intensity, hedonic value, and food association scores. The accuracy of the test was further compared to the accuracy of the established Sniffin’ Sticks identification test. The identification rates and intensities of this new FAOT were found to be comparable to the Sniffin’ Sticks olfactory identification test. The odorant pens were also assessed chemo-analytically and were found to be chemically stable for at least 24 weeks. Overall, this new identification test for use in assessing olfaction in a food-associated context is valid both in terms of its use in sensory perception studies and its chemical stability. The FOAT is particularly suited to examinations of the sense of smell regarding food odor
EVALuna2:33556
Keywords: food odorants; identification test; olfactory test; olfaction; PT-MS; smell

Distraction effects on chemosensory perception in lean and obese volunteers - Ruda, Iryna; Freiherr, Jessica (CHEMICAL SENSES, 2022)
CRIS-Team WoS Importer:2023-03-10

Elevated Insulin Levels Engage the Salience Network during Multisensory Perception - Schumann, Katja; Rodriguez-Raecke, Rea; Sijben, Rik; Freiherr, Jessica (Neuroendocrinology, 2024)
INTRODUCTION: Brain insulin reactivity has been reported in connection with systematic energy metabolism, enhancement in cognition, olfactory sensitivity, and neuroendocrine circuits. High receptor densities exist in regions important for sensory processing. The main aim of the study was to examine whether intranasal insulin would modulate the activity of areas in charge of olfactory-visual integration. METHODS: As approach, a placebo-controlled double-blind within crossover design was chosen. The experiments were conducted in a research unit of a university hospital. On separate mornings, twenty-six healthy normal-weight males aged between 19 and 31 years received either 40 IU intranasal insulin or placebo vehicle. Subsequently, they underwent 65 min of functional magnetic resonance imaging whilst performing an odor identification task. Functional brain activations of olfactory, visual, and multisensory integration as well as insulin versus placebo were assessed. Regarding the odor identification task, reaction time, accuracy, pleasantness, and intensity measurements were taken to examine the role of integration and treatment. Blood samples were drawn to control for peripheral hormone concentrations. RESULTS: Intranasal insulin administration during olfactory-visual stimulation revealed strong bilateral engagement of frontoinsular cortices, anterior cingulate, prefrontal cortex, mediodorsal thalamus, striatal, and hippocampal regions (p ≤ 0.001 familywise error [FWE] corrected). In addition, the integration contrast showed increased activity in left intraparietal sulcus, left inferior frontal gyrus, left superior frontal gyrus, and left middle frontal gyrus (p ≤ 0.013 FWE corrected). CONCLUSIONS: Intranasal insulin application in lean men led to enhanced activation in multisensory olfactory-visual integration sites and salience hubs which indicates stimuli valuation modulation. This effect can serve as a basis for understanding the connection of intracerebral insulin and olfactory-visual processing.
CRIS-Team Scopus Importer:2024-01-26
Keywords: Brain imaging; Intranasal insulin; Multisensory; Neuropeptides

Endovascular stroke treatment now and then-procedural and clinical effectiveness and safety of different mechanical thrombectomy techniques over time - Von Gadow, Niels; Nikoubashman, Omid; Freiherr, Jessica; Block, Frank; Reich, Arno; Fesl, Gunther; Wiesmann, Martin (Quantitative Imaging in Medicine and Surgery, 2017)
Background: The most essential development in endovascular stroke treatment (EST) was the shift from intra-arterial thrombolysis to endovascular thrombectomy with dedicated thrombectomy devices, most notably the introduction of stent-retrievers. We evaluated procedural and clinical effectiveness and safety of different EST techniques over time.Methods: We retrospectively analyzed EST cases that were treated by the same interventionalist before (n=36) and after (n=50) stent-retrievers were established as the treatment device of first choice. EST techniques in the first cohort comprised intra-arterial thrombolysis (n=24), manual thrombus aspiration (n=15), the use of the Penumbra thrombectomy system (n=13) and the Phenox clot retriever (n=3), intracranial stenting (n=10), and EST with stent-retrievers as a salvage procedure (n=11). In the second cohort, EST with stent-retrievers was the treatment option of first choice (n=47). Intra-arterial thrombolysis (n=15) and stenting of the occluded vessel (n=1) were performed, whenever EST with stent-retrievers failed.Results: In both cohorts, revascularization rates (TICI =2b) were high (91.7% and 86.0%, respectively). A significantly lower number of interventional techniques per case were required in the second cohort (mean +/- SD, 1.4 +/- 0.5 vs. 2.1 +/- 0.9, P<0.001). Recanalization was achieved almost twice as fast in the second cohort (85 vs. 163 minutes on average, P<0.001). The rate of patients achieving good functional outcome (mRS =2) was higher in the second cohort (40.0% vs. 22.2%, P=0.083).Conclusions: Our findings imply that when stent-retrievers were established as first-line the treatment device a significantly lower number of interventional techniques per case were required and recanalization was achieved almost twice as fast.
Keywords: Endovascular stroke treatment (EST); interventional; revascularization; stent-retriever

Erratum to: Less is more: Removing a modality of an expected olfactory-visual stimulation enhances brain activation (Human Brain Mapping, (2022), 43, 8, (2567-2581), 10.1002/hbm.25806) - Schicker, Doris; Blankenagel, Sonja; Zimmer, Claus; Hauner, Hans; Freiherr, Jessica (Human Brain Mapping, 2022)
The authors would like to correct the Acknowledgements (Schicker et al., 2022) to the following updated Acknowledgements section: We are grateful to Christoph Hofstetter and Andreas Dunkel for the development of the food preference questionnaire as well as the shared data collection using the questionnaire and for the supply of the biomimetic aroma recombinates. We would like to thank the Neuroradiology team of Klinikum Rechts der Isar for their technical support during data acquisition. We also would like to thank Kathrin Koch und Tim Rohe for fruitful discussion of the results of the study. Finally we would like to thank Alyssa Torske for language revision of the manuscript. This work was supported by a grant of the German Ministry for Education and Research (BMBF, grant no. 01EA1409A), the German Academic Scholarship Foundation, as well as the Initiative Campus of the Senses, a project with financial support of the Bavarian Ministry of Economic Affairs, Regional Development and Energy (StMWi) and the Fraunhofer Society. The present work was performed in partial fulfillment of the requirements for obtaining the degree “Dr. rer. biol. hum.” at Friedrich-Alexander-Universität Erlangen-Nürnberg. Open access funding enabled and organized by Projekt DEAL. DATA AVAILABILITY STATEMENT Data sharing is not applicable to this article as no new data were created or analyzed in this study. DATA AVAILABILITY STATEMENT Data sharing is not applicable to this article as no new data were created or analyzed in this study.
CRIS-Team Scopus Importer:2022-08-05

Eucalyptol Masks the Olfactory But Not the Trigeminal Sensation of Ammonia - Müschenich, Franziska S.; Sijben, Rik; Gallenmüller, Felix; Singer, Marco; Rodriguez-Raecke, Rea; Di Francesco, Maria Elisa; Wiesmann, Martin; Freiherr, Jessica (Chemical Senses, 2019)
Eucalyptol is a substance with rather pleasant olfactory and trigeminal characteristics and is thus suggested as an efficient tool for malodor coverage. In this study ammonia would be the malodor substance such as is found in cat litter or hair coloration. We investigated the potential of eucalyptol to inhibit both the olfactory as well as the trigeminal sensation of ammonia. For this purpose, we mixed eucalyptol and ammonia and compared odor component intensities. After being presented with either the pure odors or a binary mixture thereof, 21 young and healthy participants had to lateralize the odors and rate component (eucalyptol and ammonia) and total intensity. Analysis of intensity ratings revealed hypoadditivity (total mixture intensity was less than the sum of the total intensity of the single components). Significant interaction effects verified that mixing eucalyptol and ammonia only affected the perceived intensity of ammonia. Comparing the odor components within the pure and mixed stimuli, the ammonia component was rated as significantly less intense in the mixture compared to pure ammonia whereas the eucalyptol component was rated equal in the pure and mixed condition. On the basis of lateralization scores, we observed trigeminal mixture enhancement. We conclude that eucalyptol is a suitable masking agent to cover the unpleasant smell of ammonia; however, it fails to serve as an ammonia counterirritant because it lacks the ability to mask the trigeminal sensation of ammonia.
CRIS-Team Scopus Importer:2019-11-08
Keywords: counteraction; masking; olfactometer; olfactory receptor; trigeminal receptor

Externalization Errors of Olfactory Source Monitoring in Healthy Controls-An fMRI Study - Leclerc, Marcel P.; Kellermann, Thilo; Freiherr, Jessica; Clemens, Benjamin; Habel, Ute; Regenbogen, Christina (Chemical Senses, 2019)
Using a combined approach of functional magnetic resonance imaging (fMRI) and noninvasive brain stimulation (transcranial direct current stimulation [tDCS]), the present study investigated source memory and its link to mental imagery in the olfactory domain, as well as in the auditory domain. Source memory refers to the knowledge of the origin of mental experiences, differentiating events that have occurred and memories of imagined events. Because of a confusion between internally generated and externally perceived information, patients that are prone to hallucinations show decreased source memory accuracy; also, vivid mental imagery can lead to similar results in healthy controls. We tested source memory following cathodal tDCS stimulation using a mental imagery task, which required participants to perceive or imagine a set of the same olfactory and auditory stimuli during fMRI. The supplementary motor area (SMA) is involved in mental imagery across different modalities and potentially linked to source memory. Therefore, we attempted to modulate participants' SMA activation before entering the scanner using tDCS to influence source memory accuracy in healthy participants. Our results showed the same source memory accuracy between the olfactory and auditory modalities with no effects of stimulation. Finally, we found SMA's subregions differentially involved in olfactory and auditory imagery, with activation of dorsal SMA correlated with auditory source memory.
CRIS-Team Scopus Importer:2019-10-25
Keywords: fMRI; reality monitoring; tDCS

Fast Olfactory Threshold Determination Using an Ascending Limits Procedure - Sijben, Rik; Panzram, Claudia; Rodriguez-Raecke, Rea; Haarmeier, Thomas; Freiherr, Jessica (Chemosensory Perception, 2018)
The Sniffin' Sticks test battery is currently considered the best alternative for the measurement of olfactory threshold, discrimination and identification capabilities. These tests still suffer from limitations, however. Most noticeably, the olfactory threshold test is an intensive task which requires participants to smell a large number of olfactory stimuli. This proves especially problematic when measuring olfactory performance of elderly patients or screening research subjects, as sensory adaptation plays an important role in olfactory perception.In the current study, we have determined that the cause of this limitation lies with the test's single-staircase procedure (SSP). Consequentially, we have devised an alternative ascending limits procedure (ALP). We here compared data obtained using both procedures, following a within-subject design with 40 participants. Olfactory threshold scores as well as number of trials required to complete the two procedures were investigated.The results show that the ALP provides reliable and correct olfactory threshold ratings, as the values showed a good correlation with those obtained using the SSP and mean values did not differ significantly. Task duration, however, did show a highly significant difference, completing the SSP required participants to complete over 40% more trials compared to the ALP.The here presented methodological improvement can save time and, more importantly, reduce participants' cognitive and sensory strain, which is not only more comfortable, but also limits the influence of adaptation, making any measured data more reliable.Improving standard screening methods can directly enhance the reliability of any future study using this procedure.
Keywords: Sniffin' Sticks; TDI; Psychophysics; n-butanol; Threshold

Frequency and appearance of hemosiderin depositions after aneurysmal subarachnoid hemorrhage treated by endovascular therapy - Falter, Bernhard; Wiesmann, Martin; Freiherr, Jessica; Nikoubashman, Omid; Mull, Michael (Neuroradiology, 2015)
It is still unclear how often subarachnoid hemorrhage (SAH) leads to chronic hemosiderin depositions. In this study, we aimed to determine the frequency of chronic hemosiderin depositions after aneurysmal SAH in patients who did not undergo surgery. Furthermore, we analyzed typical MRI patterns of chronic SAH and sought to obtain information on the temporal course of MRI signal changes.We retrospectively analyzed 90 patients who had undergone endovascular treatment for acute aneurysmal SAH. In all patients, initial CT studies and at least one T2*-weighted MRI obtained 6 months or later after SAH were analyzed for the presence and anatomical distribution of SAH or chronic hemosiderin depositions. In total, 185 T2*-weighted MRI studies obtained between 2 days and 148 months after SAH were evaluated (mean follow-up 30.2 months).On MRI studies obtained later than 6 months after SAH, subpial hemosiderin depositions were found in 50 patients (55.5 %). Most frequent localizations were the parenchyma adjacent to the frontal and parietal sulci and the insular cisterns. While the appearance of hemosiderin depositions was dynamic within the first 3 months, no changes were found during subsequent follow-up. MR signal changes were not only conclusive with subarachnoid hemosiderin depositions but in many cases also resembled those that have been associated with cortical hemosiderosis.T2*-weighted MRI is an effective means of diagnosing prior SAH. Our study suggests that chronic hemosiderin depositions can be found in a considerable number of patients after a single event of subarachnoid hemorrhage.
Keywords: Hemosiderin; Endovascular therapy; T2*w magnetic resonance imaging; Subarachnoid hemorrhage; Aneurysm

Functional connectivity during multi-modal perception depends on congruency - Sijben, Rik; Hoffmann-Hensel, Sonja Maria; Rodriguez-Raecke, Rea; Freiherr, Jessica (Chemical Senses, 2018)

Functional neural processing of emotional chemosignals communicating aggression in humans - Mutic, Smiljana; Rodriguez-Raecke, Rea; Freiherr, Jessica (Chemical Senses, 2016)

Gender-Dependent Crossmodal Interactions Between Olfactory and Tactile Stimulation Revealed Using the Unimodal Tactile Stimulation Device (UniTaSD) - Sijben, Rik; Hensel, Sonja M.; Rodriguez-Raecke, Rea; Freiherr, Jessica (Chemical Senses, 2021)
Due to the complex stimulation methods required, olfaction and touch are 2 relatively understudied senses in the field of perceptual (neuro-)science. In order to establish a consistent presentation method for the bimodal stimulation of these senses, we combined an olfactometer with the newly developed Unimodal Tactile Stimulation Device. This setup allowed us to study the influence of olfaction on tactile perception and opened up an unexplored field of research by examining the crossmodal influence of tactile stimuli on olfaction. Using a pseudorandomized design, we analyzed how positive or negative tactile and olfactory stimuli influenced the opposing modality's perceived intensity and pleasantness. By asking participants to rate tactile stimuli, we were able to reproduce previously reported differences indicating that bimodal presentation with an olfactory stimulus increases or reduces perceived tactile pleasantness in an odor-dependent manner while highlighting that this effect appears unique to women. Furthermore, we found the first evidence for the influence of tactile stimuli on perceived odor pleasantness, an effect that is also driven primarily by women in our study. Based on these findings we believe that future neurophysiological studies, using controlled stimulus presentation can help unravel how and why olfactory and tactile perception interact in the human brain.
CRIS-Team Scopus Importer:2021-04-19
Keywords: crossmodal interaction; olfaction; perception; tactile; touch

Implicit Affective Rivalry: A Behavioral and fMRI Study Combining Olfactory and Auditory Stimulation - Berthold-Losleben, Mark; Habel, Ute; Brehl, Anne-Kathrin; Freiherr, Jessica; Losleben, Katrin; Schneider, Frank; Amunts, Katrin; Kohn, Nils (Frontiers in Behavioral Neuroscience, 2018)
Aversive odors are highly salient stimuli that serve a protective function. Thus, emotional reactions elicited by negative odors may be hardly influenceable. We aim to elucidate if negative mood induced by negative odors can be modulated automatically by positively valenced stimuli. We included 32 healthy participants (16 men) in an fMRI design combining aversive and neutral olfactory stimuli with positive and neutral auditory stimuli to test the influence of aversive olfactory stimuli on subjective emotional state and brain activation when combined with positive and neutral auditory stimuli. The behavioral results show an interaction of negative olfactory stimuli on ratings of disgust, perceived valence of music, and subjective affective state, while positive auditory stimulation did not show this interaction. On a neuronal level, we observed main effects for auditory and olfactory stimulation, which are largely congruent with previous literature. However, the pairing of both stimuli was associated with attenuated brain activity in a set of brain areas (supplementary motor area, temporal pole, superior frontal gyrus) which overlaps with multisensory processing areas and pave the way for automatic emotion regulation. Our behavioral results and the integrated neural patterns provide evidence of predominance of olfaction in processing of affective rivalry from multiple sensory modalities.
Keywords: music; olfaction; fMRI; emotion regulation; gender

Insulin resistance is associated with reduced food odor sensitivity across a wide range of body weights - Poessel, Maria; Freiherr, Jessica; Wiencke, Kathleen; Villringer, Arno; Horstmann, Annette (Nutrients, 2020)
The worldwide obesity epidemic is a major health problem driven by the modern food environment. Recently, it has been shown that smell perception plays a key role in eating behavior and is altered in obesity. However, the underlying mechanisms of this phenomenon are not well understood yet. Since the olfactory system is closely linked to the endocrine system, we hypothesized that hormonal shifts in obesity might explain this relationship. In a within-subject, repeated-measures design, we investigated sensitivity to a food and a non-food odor in the hungry and sated state in 75 young healthy (26 normal weight, 25 overweight, and 24 obese) participants (37 women). To determine metabolic health status and hormonal reactivity in response to food intake, we assessed pre-and postprandial levels of insulin, leptin, glucose, and ghrelin. Odor sensitivity did not directly depend on body weight status/body mass index (BMI) or hunger state. However, we could establish a strong negative mediating effect of insulin resistance on the relationship between BMI/waist-hip ratio and olfactory sensitivity for the food odor. These findings indicate an impact of metabolic health status on sensitivity to food odors. Our results contribute to a better understanding of the mechanisms behind altered smell perception in obesity.
CRIS-Team Scopus Importer:2020-08-07
Keywords: HOMA-IR; Insulin resistance; Obesity; Odor sensitivity; Olfaction

Intramodal Olfactory Priming of Positive and Negative Odors in Humans Using Respiration-Triggered Olfactory Stimulation (RETROS) - Hoffmann-Hensel, Sonja Maria; Freiherr, Jessica (Chemical Senses, 2016)
Priming describes the principle of modified stimulus perception that occurs due to a previously presented stimulus. Although we have begun to understand the mechanisms of crossmodal priming, the concept of intramodal olfactory priming remains relatively unexplored. Therefore, we applied positive and negative odors using respiration-triggered olfactory stimulation (RETROS), enabling us to record the skin conductance response (SCR) and breathing data without a crossmodal cueing error and measure reaction times (RTs) for olfactory tasks. RT, SCR, and breathing data revealed that negative odors were perceived significantly more arousing than positive ones. In a second experiment, 2 odors were applied during consecutive respirations. Here, we observed intramodal olfactory priming effects: A negative odor preceded by a positive odor was rated as more pleasant than when the same odor was preceded by a negative odor. Additionally, a longer identification RT was found for the second compared with the first odor. We interpret this as increased "perceptual load" due to incomplete first odor processing while the second odor was presented. Furthermore, intramodal priming can be considered a possible reason for the increase of identification RT. The use of RETROS led to these novel insights into olfactory processing beyond crossmodal interaction by providing a noncued unimodal olfactory test, and therefore, RETROS can be used in the experimental design of future olfactory studies.
Keywords: intramodal priming; olfaction; respiration; skin conductance response

Intranasal Insulin as a Treatment for Alzheimer's Disease: A Review of Basic Research and Clinical Evidence - Freiherr, Jessica; Hallschmid, Manfred; Frey, William H.; Bruenner, Yvonne F.; Chapman, Colin D.; Hoelscher, Christian; Craft, Suzanne; De Felice, Fernanda G.; Benedict, Christian (Cns Drugs, 2013)
Research in animals and humans has associated Alzheimer's disease (AD) with decreased cerebrospinal fluid levels of insulin in combination with decreased insulin sensitivity (insulin resistance) in the brain. This phenomenon is accompanied by attenuated receptor expression of insulin and insulin-like growth factor, enhanced serine phosphorylation of insulin receptor substrate-1, and impaired transport of insulin across the blood-brain barrier. Moreover, clinical trials have demonstrated that intranasal insulin improves both memory performance and metabolic integrity of the brain in patients suffering from AD or its prodrome, mild cognitive impairment. These results, in conjunction with the finding that insulin mitigates hippocampal synapse vulnerability to beta amyloid, a peptide thought to be causative in the development of AD, provide a strong rationale for hypothesizing that pharmacological strategies bolstering brain insulin signaling, such as intranasal administration of insulin, could have significant potential in the treatment and prevention of AD. With this view in mind, the review at hand will present molecular mechanisms potentially underlying the memory-enhancing and neuroprotective effects of intranasal insulin. Then, we will discuss the results of intranasal insulin studies that have demonstrated that enhancing brain insulin signaling improves memory and learning processes in both cognitively healthy and impaired humans. Finally, we will provide an overview of neuroimaging studies indicating that disturbances in insulin metabolism-such as insulin resistance in obesity, type 2 diabetes and AD-and altered brain responses to insulin are linked to decreased cerebral volume and especially to hippocampal atrophy.

Intranasal Insulin Boosts Gustatory Sensitivity - Rodriguez-Raecke, Rea; Yang, H.; Bruenner, Y. F.; Freiherr, Jessica (Journal of Neuroendocrinology, 2017)
Intranasal insulin has been the subject of attention not only with respect to enhancing memory processes, but also for its anorexic effects, as well as its effects on olfactory sensitivity. In the present study, the influence of intranasal insulin on gustatory sensitivity was investigated using intranasal applications of insulin or placebo in a double-blind manner alongside a control condition without any application. We hypothesised that, because it mediates satiety, intranasal insulin alters gustatory sensitivity, whereas placebo application and the control should not alter gustatory sensitivity. We did not expect the sensitivity to the different taste solutions to differ. Sweet, salty, bitter and sour liquids in four concentrations each were sprayed onto the tongue of healthy male subjects. Additionally, water with no taste was applied to enable calculation of taste sensitivity in terms of parameter d' of signal detection theory. The task of the subject was to identify the quality of the respective tastant. Gustatory sensitivity and blood parameters were evaluated using repeated-measures ANOVAs. Gustatory sensitivity (implying all tastants) improved significantly after intranasal insulin application compared to the application of placebo, although it did not reach significance compared to the control condition. Subjects performed best when detecting the sweet taste and worst when detecting the bitter taste. The blood parameters glucose, insulin, homeostatic model assessment and leptin did not differ with respect to insulin or placebo condition, nor did they differ regarding measurements preceding or following intranasal application, in confirmation of preserved peripheral euglycaemia during the experiment. Thus, it can be concluded that the application of intranasal insulin led to an improved gustatory sensitivity compared to placebo.
Keywords: intranasal insulin application; gustation; taste

Intranasal insulin influences the olfactory performance of patients with smell loss, dependent on the body mass index: A pilot study - Schoepf, V.; Kollndorfer, Kathrin; Pollak, M.; Mueller, C. A.; Freiherr, Jessica (Rhinology, 2015)
Background: The application of intranasal insulin in healthy humans has been linked to improved memory function, reduced food intake, and increased olfactory thresholds, There has also been some correlation between the morbidities associated with central nervous system (CNS) insulin resistance, such as type II diabetes mellitus, Alzheimer's disease, obesity, and impaired odour recognition. Given that impaired odour recognition is an important component of olfactory performance, mechanisms that govern these effects may account for impaired olfactory functions in anosmic patients.Methodology:Ten patients with post-infectious olfactory loss received intranasal administration of 40 IU insulin or a placebo solution, as well as olfactory performance tests before and after administration.Results: When administered insulin, patients exhibited an immediate performance improvement with regard to olfactory sensitivity and olfactory intensity ratings. In addition, more odours were correctly identified. Furthermore, an improvement in the odour identification task was detected in patients with higher body mass index.Conclusion: Results of this pilot study shed light on the link between cerebral insulin level and an impaired sense of smell.This research line might provide a better understanding of olfactory loss in relation to eating and dietary behavior, and could offer opportunities to develop faster therapeutic intervention for patients with olfactory dysfunction.
Keywords: anosmia; olfactory dysfunction; metabolic influence; intranasal insulin; smell; olfaction

Intranasal Insulin Reduces Olfactory Sensitivity in Normosmic Humans - Bruenner, Yvonne F.; Benedict, Christian; Freiherr, Jessica (Journal of Clinical Endocrinology and Metabolism, 2013)
Context: High densities of insulin receptors are found throughout the human brain, including the olfactory bulb, an essential brain area for odor processing. This brain region is the phylogenetically oldest part of the olfactory central nervous system.Objective: We hypothesized that enhanced brain insulin signaling would modulate olfactory processing in humans.Design: We applied a double-blind, placebo-controlled, balanced within-subject design.Setting: This study was conducted in the research unit of a university hospital.Interventions/Participants/Main Outcome Measures: A single dose of either insulin (40 IU) or placebo was intranasally administered to 17 normal-weight normosmic participants (7 women). Subjects' olfactory abilities were examined by means of an olfactory threshold test (odorant n-butanol) and an olfactory discrimination test. In addition, circulating concentrations of glucose, insulin, and cortisol levels were measured.Results: After intranasal insulin administration, subjects' sensitivity for the odorant n-butanol was significantly decreased compared with that for the placebo condition (-13%; P = .025), whereas olfactory discrimination ability was not (P = .841). While serum insulin and serum cortisol were not altered after intranasal insulin administration, there was a small but significant drop in plasma glucose levels. Importantly, a correlational analysis demonstrated that this treatment-induced drop in plasma glucose was not related to the effects of intranasal insulin on olfactory sensitivity.Conclusions: These findings suggest that intranasal insulin impairs olfactory sensitivity for a non-food odorant, whereas no such effects were found for olfactory discrimination. Thus, variations in brain insulin signaling most likely have implications for the olfactory threshold of normosmic humans. Bearing in mind the fact that insulin acts as an anorexigenic signal in the human brain, further studies are needed to test whether intranasal insulin also impairs the ability of humans to perceive food-related odors.

Less is more: Removing a modality of an expected olfactory-visual stimulation enhances brain activation - Schicker, Doris; Blankenagel, Sonja; Zimmer, Claus; Hauner, Hans; Freiherr, Jessica (Human Brain Mapping, 2022)
In recent years, multisensory integration of visual and olfactory stimuli has extensively been explored resulting in the identification of responsible brain areas. As the experimental designs of previous research often include alternating presentations of unimodal and bimodal stimuli, the conditions cannot be regarded as completely independent. This could lead to effects of an expected but surprisingly missing sensory modality. In our experiment, we used a common functional magnetic resonance imaging (fMRI) study design with alternating strong unimodal and bimodal olfactory-visual food stimuli, in addition to a slight overhang of the bimodal stimuli in an effort to examine the effects of removing a visual or olfactory congruent stimulus for older people (41–83 years). Our results suggest that the processing of olfactory and visual stimuli stays intact over a wide age-range and that the utilization of strong stimuli does not lead to superadditive multisensory integration in accordance with the principle of inverse effectiveness. However, our results demonstrate that the removal of a stimulus modality leads to an activation of additional brain areas. For example, when the visual stimulus modality is missing, the right posterior superior temporal gyrus shows higher activation, whereas the removal of the olfactory stimulus modality leads to higher activation in the amygdala/hippocampus and the postcentral gyrus. These brain areas are related to attention, memory, and the search of the missing stimulus. Consequently, careful attention must be paid to the design of a valid, multimodal sensory experiment while also controlling for cognitive expectancy effects that might confound multimodal results.
CRIS-Team Scopus Importer:2022-02-25
Keywords: expectations; fMRI; multisensory; olfaction; stimulus removal; vision

Less is More: Stimulus Removal in Olfactory-Visual Stimulation Increases Activation in Multisensory Brain Areas - Schicker, Doris; Blankenagel, Sonja; Zimmer, Claus; Hauner, Hans; Freiherr, Jessica (CHEMICAL SENSES, 2021)
CRIS-Team WoS Importer:2021-12-24

Measurement of Stress Relief during Scented Cosmetic Product Application Using a Mood Questionnaire, Stress Hormone Levels and Brain Activation - Springer, Arielle; Hoeckmeier, Laura; Schicker, Doris; Hettwer, Stefan; Freiherr, Jessica (Cosmetics, 2022)
Nowadays, consumers’ well-being plays a decisive role in the purchase of cosmetic products. Although factors influencing consumers’ well-being are very subjective, companies strive to develop their products in such a way that a positive effect is likely. Therefore, methods are required to objectively explore and scientifically prove the product’s performance on humans. In this placebo-controlled study, a method was developed to evaluate relaxation or stress relief associated with one olfactory ingredient of a cosmetic product (face cream). Our experimental protocol included product testing in 25 healthy females, while an emotion questionnaire, analysis of saliva samples regarding the concentration of the hormones cortisol and α-amylase and mobile EEG measurement for quantification of the alpha brain waves before and after stress induction were conducted. It was shown that with this experimental design, the sample with the ingredient produced significant stress relief, as evidenced by significantly less negative emotion, significantly lowered cortisol levels and showed a trend towards a significant increase in alpha activity compared to placebo application. Our data provide evidence that this method is suitable for analyzing the differences between the two samples. In the future, this method can be utilized in the current or a further optimized form to evaluate the psychophysiological effects of cosmetic products on humans.
CRIS-Team Scopus Importer:2022-11-04
Keywords: alpha waves; amylase; aroma; brain activity; cortisol; EEG; fragrance; neuroscience; positive mood; relaxation; scent; skin care; well-being

Modulation of odor-cued memory processing by intranasal insulin - Bruenner, Yvonne F.; Rodriguez-Raecke, Rea; Benedict, Christian; Freiherr, Jessica (Chemical Senses, 2015)

More Than Smell-COVID-19 Is Associated With Severe Impairment of Smell, Taste, and Chemesthesis - Parma, Valentina; Ohla, Kathrin; Veldhuizen, Maria G.; Niv, Masha Y.; Kelly, Christine E.; Bakke, Alyssa J.; Cooper, Keiland W.; Bouysset, Cédric; Pirastu, Nicola; Dibattista, Michele; Kaur, Rishemjit; Liuzza, Marco Tullio; et al. (Chemical Senses, 2020)
Recent anecdotal and scientific reports have provided evidence of a link between COVID-19 and chemosensory impairments, such as anosmia. However, these reports have downplayed or failed to distinguish potential effects on taste, ignored chemesthesis, and generally lacked quantitative measurements. Here, we report the development, implementation, and initial results of a multilingual, international questionnaire to assess self-reported quantity and quality of perception in 3 distinct chemosensory modalities (smell, taste, and chemesthesis) before and during COVID-19. In the first 11 days after questionnaire launch, 4039 participants (2913 women, 1118 men, and 8 others, aged 19-79) reported a COVID-19 diagnosis either via laboratory tests or clinical assessment. Importantly, smell, taste, and chemesthetic function were each significantly reduced compared to their status before the disease. Difference scores (maximum possible change ±100) revealed a mean reduction of smell (-79.7 ± 28.7, mean ± standard deviation), taste (-69.0 ± 32.6), and chemesthetic (-37.3 ± 36.2) function during COVID-19. Qualitative changes in olfactory ability (parosmia and phantosmia) were relatively rare and correlated with smell loss. Importantly, perceived nasal obstruction did not account for smell loss. Furthermore, chemosensory impairments were similar between participants in the laboratory test and clinical assessment groups. These results show that COVID-19-associated chemosensory impairment is not limited to smell but also affects taste and chemesthesis. The multimodal impact of COVID-19 and the lack of perceived nasal obstruction suggest that severe acute respiratory syndrome coronavirus strain 2 (SARS-CoV-2) infection may disrupt sensory-neural mechanisms.
CRIS-Team Scopus Importer:2020-10-30
Keywords: head and neck surgery; olfaction; somatosensation

Multisensory integration mechanisms during aging - Freiherr, Jessica; Lundstrom, Johan N.; Habel, Ute; Reetz, Kathrin (Frontiers in Human Neuroscience, 2013)
The rapid demographical shift occurring in our society implies that understanding of healthy aging and age-related diseases is one of our major future challenges. Sensory impairments have an enormous impact on our lives and are closely linked to cognitive functioning. Due to the inherent complexity of sensory perceptions, we are commonly presented with a complex multisensory stimulation and the brain integrates the information from the individual sensory channels into a unique and holistic percept. The cerebral processes involved are essential for our perception of sensory stimuli and becomes especially important during the perception of emotional content. Despite ongoing deterioration of the individual sensory systems during aging, there is evidence for an increase in, or maintenance of, multisensory integration processing in aging individuals. Within this comprehensive literature review on multisensory integration we aim to highlight basic mechanisms and potential compensatory strategies the human brain utilizes to help maintain multisensory integration capabilities during healthy aging to facilitate a broader understanding of age-related pathological conditions. Further our goal was to identify where further research is needed.
Keywords: crossmodal sensory integration; cognition; multimodal; aging neuroscience; elderly population; multisensory integration

Multisensory integration processing during olfactory-visual stimulation-An fMRI graph theoretical network analysis - Ripp, Isabelle; Zur Nieden, Anna-Nora; Blankenagel, Sonja; Franzmeier, Nicolai; Lundstrom, Johan N.; Freiherr, Jessica (Human Brain Mapping, 2018)
In this study, we aimed to understand how whole-brain neural networks compute sensory information integration based on the olfactory and visual system. Task-related functional magnetic resonance imaging (fMRI) data was obtained during unimodal and bimodal sensory stimulation. Based on the identification of multisensory integration processing (MIP) specific hub-like network nodes analyzed with network-based statistics using region-of-interest based connectivity matrices, we conclude the following brain areas to be important for processing the presented bimodal sensory information: right precuneus connected contralaterally to the supramarginal gyrus for memory-related imagery and phonology retrieval, and the left middle occipital gyrus connected ipsilaterally to the inferior frontal gyrus via the inferior fronto-occipital fasciculus including functional aspects of working memory. Applied graph theory for quantification of the resulting complex network topologies indicates a significantly increased global efficiency and clustering coefficient in networks including aspects of MIP reflecting a simultaneous better integration and segregation. Graph theoretical analysis of positive and negative network correlations allowing for inferences about excitatory and inhibitory network architectures revealednot significant, but very consistentthat MIP-specific neural networks are dominated by inhibitory relationships between brain regions involved in stimulus processing.
Keywords: functional imaging; graph theory; functional connectivity; network efficiency; beta-series correlation; network statistics

Multisensory Perception Food: Taste the smell, hear the Picture - the close Connection of our Senses - Blankenagel, Sonja; Freiherr, Jessica (Deutsche Lebensmittel-Rundschau, 2017)

Neural correlates of olfactory and visual memory performance in 3D-simulated mazes after intranasal insulin application - Bruenner, Yvonne F.; Rodriguez-Raecke, Rea; Mutic, Smiljana; Benedict, Christian; Freiherr, Jessica (Neurobiology of Learning and Memory, 2016)
This fMRI study intended to establish 3D-simulated mazes with olfactory and visual cues and examine the effect of intranasally applied insulin on memory performance in healthy subjects. The effect of insulin on hippocampus-dependent brain activation was explored using a double-blind and placebo-controlled design. Following intranasal administration of either insulin (40 ID) or placebo, 16 male subjects participated in two experimental MRI sessions with olfactory and visual mazes. Each maze included two separate runs. The first was an encoding maze during which subjects learned eight olfactory or eight visual cues at different target locations. The second was a recall maze during which subjects were asked to remember the target cues at spatial locations. For eleven included subjects in the fMRI analysis we were able to validate brain activation for odor perception and visuospatial tasks. However, we did not observe an enhancement of declarative memory performance in our behavioral data or hippocampal activity in response to insulin application in the fMRI analysis. It is therefore possible that intranasal insulin application is sensitive to the methodological variations e.g. timing of task execution and dose of application. Findings from this study suggest that our method of 3D-simulated mazes is feasible for studying neural correlates of olfactory and visual memory performance. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: Olfaction; Hippocampus activation; Intranasal insulin; Spatial memory

Neuroimaging of smell and taste - Olofsson, Jonas K.; Freiherr, Jessica (Handbook of Clinical Neurology, 2019)
The senses of taste and smell developed early in evolution and are of high ecological and clinical relevance in humans. Chemosensory systems function, in large part, as hazard avoidance systems, thereby ensuring survival. Moreover, they play a critical role in nutrition and in determining the flavor of foods and beverages. Their dysfunction has been shown to be a key element of early stages of a number of diseases, including Alzheimer's and Parkinson's diseases. Advanced neuroimaging methods provide a unique means for understanding, in vivo, neural and psychological processing of smell, taste, and flavor, and how diseases can impact such processing. This chapter provides, from a neuroimaging perspective, a comprehensive overview of the anatomy and physiology involved in the odor and taste processing in the central nervous system. Some methodological challenges associated with chemosensory neuroimaging research are discussed. Multisensory integration, the mechanisms that enable holistic sensory experiences, is emphasized.
CRIS-Team Scopus Importer:2019-10-15
Keywords: Attention; Flavor; Functional imaging; Gustation; Gustometer; Multisensory integration; Odor; Olfaction; Olfactometer; Reward

Neuronal processing of malodor coverage - Rodriguez-Raecke, R.; Loos, H.; Sijben, R.; Buettner, A.; Singer, M.; Freiherr, Jessica (Chemical Senses, 2017)

New similarity search based glioma grading - Haegler, Katrin; Wiesmann, Martin; Boehm, Christian; Freiherr, Jessica; Schnell, Oliver; Brueckmann, Hartmut; Tonn, Joerg-Christian; Linn, Jennifer (Neuroradiology, 2012)
MR-based differentiation between low- and high-grade gliomas is predominately based on contrast-enhanced T1-weighted images (CE-T1w). However, functional MR sequences as perfusion- and diffusion-weighted sequences can provide additional information on tumor grade. Here, we tested the potential of a recently developed similarity search based method that integrates information of CE-T1w and perfusion maps for non-invasive MR-based glioma grading.We prospectively included 37 untreated glioma patients (23 grade I/II, 14 grade III gliomas), in whom 3T MRI with FLAIR, pre- and post-contrast T1-weighted, and perfusion sequences was performed. Cerebral blood volume, cerebral blood flow, and mean transit time maps as well as CE-T1w images were used as input for the similarity search. Data sets were preprocessed and converted to four-dimensional Gaussian Mixture Models that considered correlations between the different MR sequences. For each patient, a so-called tumor feature vector (= probability-based classifier) was defined and used for grading. Biopsy was used as gold standard, and similarity based grading was compared to grading solely based on CE-T1w.Accuracy, sensitivity, and specificity of pure CE-T1w based glioma grading were 64.9%, 78.6%, and 56.5%, respectively. Similarity search based tumor grading allowed differentiation between low-grade (I or II) and high-grade (III) gliomas with an accuracy, sensitivity, and specificity of 83.8%, 78.6%, and 87.0%.Our findings indicate that integration of perfusion parameters and CE-T1w information in a semi-automatic similarity search based analysis improves the potential of MR-based glioma grading compared to CE-T1w data alone.
Keywords: Glioma grading; Perfusion MRI; Similarity search; Gaussian Mixture Model

Nutrition claims influence expectations about food attributes, attenuate activity in reward-associated brain regions during tasting, but do not impact pleasantness - Rramani, Qendresa; Barakat, Youssef; Jacob, George; Ohla, Kathrin; Lim, Shirley Xue Li; Schicker, Doris; Freiherr, Jessica; Saruco, Elodie; Pleger, Burkhard; Weber, Bernd; Schultz, Johannes (Brain and Behavior, 2022)
IntroductionNutrition claims are one of the most common tools used to improve food decisions. Previous research has shown that nutrition claims impact expectations; however, their effects on perceived pleasantness, valuation, and their neural correlates are not well understood. These claims may have both intended and unintended effects on food perception and valuation, which may compromise their effect on food decisions. MethodsWe investigated the effects of nutrition claims on expectations, perceptions, and valuation of milk-mix drinks in a behavioral (n = 110) and an fMRI (n = 39) study. In the behavioral study, we assessed the effects of a "fat-reduced" and a "protein-rich" nutrition claim on expected and perceived food attributes of otherwise equal food products. In the fMRI study, we investigated the effect of a "protein-rich" claim on taste pleasantness perception and valuation, and on their neural correlates during tasting and swallowing. ResultsWe found that both nutrition claims increased expected and perceived healthiness and decreased expected but not perceived taste pleasantness. The "protein-rich" claim increased expected but not perceived satiating quality ratings, while the "fat-reduced" claim decreased both expected and perceived satiating quality ratings. In the absence vs. presence of the "protein-rich" claim, we observed an increased activity in a cluster extending to the left nucleus accumbens during tasting and an increased functional connectivity between this cluster and a cluster in right middle frontal gyrus during swallowing. ConclusionAltogether, we found that nutrition claims impacted expectations and attenuated reward-related responses during tasting but did not negatively affect perceived pleasantness. Our findings support highlighting the presence of nutrients with positive associations and exposure to foods with nutrition claims to increase their acceptance. Our study offers insights that may be valuable in designing and optimizing the use of nutrition claims.
CRIS-Team WoS Importer:2022-12-30

Odor Object-related Activity in PPC Increases with the Number of Stimulated Senses - Porada, Danja; Regenbogen, Christina; Freiherr, Jessica; Lundstrom, Johan N. (Chemical Senses, 2017)

Odor Sensitivity After Intranasal Insulin Application Is Modulated by Gender - Rodriguez-Raecke, Rea; Bruenner, Yvonne F.; Kofoet, Anja; Mutic, Smiljana; Benedict, Christian; Freiherr, Jessica (Frontiers in Endocrinology, 2018)
Obesity constitutes a global health care problem, and often eating habits are to blame. For intervention, a thorough understanding of energy intake and expenditure is needed. In recent years, the pivotal role of insulin in connection to energy intake was established. Olfactory sensitivity may be a target of cerebral insulin action to maintain body weight. With this experiment, we aimed to explore the influence of intranasal insulin on olfactory sensitivity for the odors n-butanol and peanut in a placebo-controlled, double-blind setting in a within-subject design. All subjects participated in two experimental sessions on separate days and received either intranasal insulin or placebo in a pseudorandomized order. Application was followed by two olfactory threshold tests for n-butanol and peanut in a pseudorandomized order. After a single dose of intranasal insulin (40 IU) or placebo (0.4 ml), olfactory sensitivity for the odorants n-butanol and peanut were examined in 30 healthy normosmic participants (14 females). Measured blood parameters revealed no decrease in plasma glucose, however, insulin, leptin and cortisol levels were affected following intranasal application. Females' but not males' olfactory sensitivity for n-butanol was lower after intranasal insulin administration vs. placebo. In contrast, olfactory sensitivity for peanut was not influenced by intranasal insulin application. Our results indicate that the effects of cortical insulin levels on processing of specific odors is likely modulated by gender, as central increase of insulin concentration led to a reduced olfactory sensitivity for n-butanol in women only, which might be due to differentially regulated insulin and leptin signaling in men and women.
Keywords: intranasal insulin; odor sensitivity; olfaction; olfactory threshold; n-butanol; peanut

Olfactory functioning in adults with Tourette syndrome - Kronenbuerger, Martin; Belenghi, Patrizia; Ilgner, Justus; Freiherr, Jessica; Hummel, Thomas; Neuner, Irene (PLoS ONE, 2018)
Tourette syndrome is a chronic tic disorder characterized by motor and vocal tics. Comorbidities such as attention deficit hyperactivity disorder and obsessive compulsive disorder can be found. The overlap between neuroanatomical regions and neurotransmitter systems in the olfactory system and the pathophysiology of Tourette syndrome let us hypothesize altered olfactory performance in Tourette syndrome. The main objective of this study was to systematically assess olfactory functioning in subjects with Tourette syndrome and to compare it to healthy controls. We assessed 28 adults with Tourette syndrome (age 33.1 +/- 9.4 years, disease duration 23.7 +/- 9.7 years) and 28 healthy controls (age 32.9 +/- 9.0 years) matched in regard to age, sex, education and smoking habits. The "Sniffin Sticks" test battery was applied to assess odor threshold, discrimination, and identification. Additionally, the combined score of the odor threshold test, the odor discrimination test and the odor identification test of the "Sniffin Sticks" test battery was calculated. Although it was not the primary aim of this study, we assessed whether tics and comorbidity could contribute to olfactory alterations in adults with Tourette syndrome. Therefore, clinical scores were used to assess severity of tics and co-morbidity such as attention deficit hyperactivity disorder, obsessive compulsive disorder, anxiety and depression in subjects with Tourette syndrome. Pathology of the nasal cavities was excluded with rhinoendoscopy. Independent sample ttests were applied to compare performance in olfactory tests. In the case of statistically significant differences (critical p-value: 0.05), multiple linear regression analysis was carried out to explore whether tic severity, social impairment, co-morbidity or medical treatment had an impact on the differences found. Descriptive values are reported as mean +/- standard deviation. Tourette syndrome subjects showed lower combined scores (Tourette syndrome subjects 31.9 +/- 5.1 versus healthy controls 35.0 +/- 3.1; p = 0.007), odor identification scores (Tourette syndrome subjects 12.4 +/- 2.0 versus healthy controls 13.7 +/- 1.4; p = 0.008) and odor discrimination scores (Tourette syndrome subjects 12.1 +/- 2.1 versus healthy controls 13.2 +/- 1.6; p = 0.041) in comparison to healthy subjects, while there was no difference in odor threshold (Tourette syndrome subjects 7.3 +/- 2.7 versus healthy controls 8.1 +/- 2.2; p = 0.22). Seven out of 28 Tourette syndrome subjects (25%) scored in the range of the age- and sex-dependent combined score for hyposmia, while two of 28 healthy controls (7%) had a similar low combined score. None of the participants were found to have functional anosmia. Multiple linear regression analyses suggest that social impairment may a predictor for low combined score and odor identification score in Tourette syndrome subjects (p = 0.003). Compared to healthy controls, altered olfaction in adults with Tourette syndrome was found in this study. Normal odor threshold level but lower scores at tasks involving supra-threshold odor concentrations point towards a central-nervous alteration in the processing of olfactory information in Tourette syndrome.

Olfactory Function is Affected in Patients with Cirrhosis Depending on the Severity of Hepatic Encephalopathy - Heiser, Clemens; Haller, Bernhard; Sohn, Maximilian; Hofauer, Benedikt; Knopf, Andreas; Muehling, Tobias; Freiherr, Jessica; Bender, Martin; Tiller, Maximilian; Schmidt, Anna; Schepp, Wolfgang; Gundling, Felix (Annals of Hepatology, 2018)
Introduction and aim. Olfactory functions are altered to a variable degree by chronic liver disease. Few studies including only small populations of patients emphasized the possibility of hepatic encephalopathy (HE) influencing olfactory nervous tasks. So far, no study has explicitly focused on olfactory function depending on the severity of HE as assessed by objective diagnostic procedures. Thus we performed a study using the "Sniffin' Sticks" test system, critical flicker-fusion frequency (CFF) and clinical West Haven criteria. Material and methods. 54 cirrhotic patients with liver cirrhosis were included. Furthermore, 43 adult volunteers participating as a non-cirrhotic control group. Olfactory testing was performed using the "Sniffin' Stick" test battery (Burghart Medizintechnik, Wedel, Germany) which renders a widely-used tool both in clinical and research settings for the assessment of olfactory threshold, odor identification and discrimination. Several complications of cirrhosis were diagnosed by reference methods. Statistical analysis of cirrhosis-associated complications and their relation to olfactory function was performed. Assessment of HE and classification of different stages were performed according to clinical criteria (West-Haven criteria) and according to CFF, which was determined using a portable analyzer. Results. Olfactory function was significantly reduced in cirrhotic patients (in 61.1%) compared to controls (p < 0.001). Among cirrhotics patients, the prevalence of olfactory deficits (hyposmia, anosmia) increased with the severity of HE as assessed by CFF and clinical criteria (p = 0.008 and p = 0.097, respectively). No correlation was observed between olfactory deficits and severity of liver disease as assessed by Child-Pugh-Score, etiology of cirrhosis and complications of cirrhosis such as ascites and portal venous hypertension. Conclusions. Olfactory testing serves as a screening tool for HE and may faciliate grading of HE-severity.
Keywords: Hepatic encephalopathy; Chemosensation; Critical flicker frequency; Smell disorders

Olfactory-trigeminal Masking Effects - Ruda, Iryna; Muschenich, Franziska Sonja; Freiherr, Jessica (CHEMICAL SENSES, 2021)
CRIS-Team WoS Importer:2021-12-24

Olfactory-visual interference effect in patients with Autism Spectrum Disorder - Stickel, Susanne; Weismann, Pauline; Habel, Ute; Chechko, Natalia; Freiherr, Jessica (Chemical Senses, 2018)

Orbitofrontal Cortex and Olfactory Bulb Volume Predict Distinct Aspects of Olfactory Performance in Healthy Subjects - Seubert, Janina; Freiherr, Jessica; Frasnelli, Johannes; Hummel, Thomas; Lundstroem, Johan N. (Cerebral Cortex, 2013)
While recent studies suggest an important role of higher order olfactory brain areas for basic olfactory performance, the extent to which cortical and peripheral neural markers account for separate portions of the variability in olfactory perceptual acuity is still unclear. We addressed this question by correlating voxel-based morphometry data from 90 healthy adults with olfactory performance measures. Supplementing this approach with region of interest (ROI) analyses of functionally defined olfactory cortical regions and olfactory bulb volume, we sought to disentangle the relative contribution of central and peripheral areas to behavioral variability. Whole-brain analyses revealed a significant positive correlation of gray matter volume and olfactory function scores in the right orbital sulcus. This effect was confirmed by the ROI analyses, which further indicated a significant association of the olfactory score with olfactory bulb volume. Moreover, a functional dissociation was observed, with central and peripheral mechanisms explaining different aspects of the observed behavioral variance in the olfactory subscores. In line with previous clinical studies, these data thus suggest an important role of regional gray matter volume in the right orbitofrontal cortex and olfactory bulb volume for olfactory performance in healthy individuals.
Keywords: OFC; olfaction; olfactory bulb; perception; VBM

Out of the woods: psychophysiological investigations on wood odors to estimate their suitability as ambient scents - Schreiner, Linda; Karacan, Brid; Blankenagel, Sonja; Packhaeuser, Kai; Freiherr, Jessica; Loos, Helene (Wood Science and Technology, 2020)
Wood has been an important raw material for centuries, and humans encounter it in the form of furniture and building materials or in products of daily use. The odors emanating from such wood-based materials can add another facet to their functionality by influencing human well-being and mood. Moreover, wood odors can be used in odor-enhanced environments to foster relaxation and stress recovery. The current study was conducted to assess the subjective evaluation of, and physiological responses to, wood odors and individual wood odor constituents. The subjects smelled the odors of pine needles oil, cedar wood oil, α-pinene, and thymoquinone and evaluated the odor percept and their subjective feelings. Heart rate, finger temperature, and skin conductance were monitored throughout the experiment. The results showed that wood odors were distinct regarding their pleasantness, familiarity, and intensity. All odors enhanced the subjective feelings of happiness and content. Though no odor-specific physiological effects became evident, certain physiological measures correlated with self-reports of happy and relaxed feelings and the intensity ratings of the odors. The present study provides a basis for further studies on the use of wood odors as ambient scents and helps understanding the influence of natural odors on humans.
CRIS-Team Scopus Importer:2020-09-11

OWSum: algorithmic odor prediction and insight into structure-odor relationships - Schicker, Doris; Singh, Satnam; Freiherr, Jessica; Grasskamp, Andreas T. T. (Journal of Cheminformatics, 2023)
We derived and implemented a linear classification algorithm for the prediction of a molecule’s odor, called Olfactory Weighted Sum (OWSum). Our approach relies solely on structural patterns of the molecules as features for algorithmic treatment and uses conditional probabilities combined with tf-idf values. In addition to the prediction of molecular odor, OWSum provides insights into properties of the dataset and allows to understand how algorithmic classifications are reached by quantitatively assigning structural patterns to odors. This provides chemists with an intuitive understanding of underlying interactions. To deal with ambiguities of the natural language used to describe odor, we introduced descriptor overlap as a metric for the quantification of semantic overlap between descriptors. Thus, grouping of descriptors and derivation of higher-level descriptors becomes possible. Our approach poses a large leap forward in our capabilities to understand and predict molecular features.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Odor prediction; Olfaction; Structure-odor relationships

Performance of a Deep-Learning Neural Network to Detect Intracranial Aneurysms from 3D TOF-MRA Compared to Human Readers. - Faron, Anton; Sichtermann, Thorsten; Teichert, Nikolas; Luetkens, Julian A.; Keulers, Annika; Nikoubashman, Omid; Freiherr, Jessica; Mpotsaris, Anastasios; Wiesmann, Martin (Clinical Neuroradiology, 2020)
To study the clinical potential of a deep learning neural network (convolutional neural networks [CNN]) as a supportive tool for detection of intracranial aneurysms from 3D time-of-flight magnetic resonance angiography (TOF-MRA) by comparing the diagnostic performance to that of human readers.In this retrospective study a pipeline for detection of intracranial aneurysms from clinical TOF-MRA was established based on the framework DeepMedic. Datasets of 85 consecutive patients served as ground truth and were used to train and evaluate the model. The ground truth without annotation was presented to two blinded human readers with different levels of experience in diagnostic neuroradiology (reader 1: 2 years, reader 2: 12 years). Diagnostic performance of human readers and the CNN was studied and compared using the ?-test and Fishers' exact test.Ground truth consisted of 115 aneurysms with a mean diameter of 7 mm (range: 2-37 mm). Aneurysms were categorized as small (S; <3 mm; N = 13), medium (M; 3-7 mm; N = 57), and large (L; >7 mm; N = 45) based on the diameter. No statistically significant differences in terms of overall sensitivity (OS) were observed between the CNN and both of the human readers (reader 1 vs. CNN, P = 0.141; reader 2 vs. CNN, P = 0.231). The OS of both human readers was improved by combination of each readers' individual detections with the detections of the CNN (reader 1: 98% vs. 95%, P = 0.280; reader 2: 97% vs. 94%, P = 0.333).A CNN is able to detect intracranial aneurysms from clinical TOF-MRA data with a sensitivity comparable to that of expert radiologists and may have the potential to improve detection rates of incidental findings in a clinical setting.
EVALuna2:280563

Playing Tetris Lets You Rate Odors as Less Intense - Schadll, Stephan; Rodriguez-Raecke, Rea; Heim, Lennart; Freiherr, Jessica (Frontiers in Psychology, 2021)
Overweight and obesity are considered a huge problem in modern societies. Previous studies have shown that people who are regularly distracted by playing videogames or watching TV while eating are more likely to be overweight and that the number of people that are gaming worldwide is rising. Further, it has been established that both, watching TV or playing video games lead to an increased snack intake and a lower rating of perceived taste intensity. Since flavor perception is accomplished not only by the sense of taste but also the sense of smell, we investigated the influence of cognitive load created by playing a video game on odor intensity perception. The participants played a low or high difficulty version of Tetris while presented with odors of food and non-food items. A higher skin conductance response (SCR) along with a decrease in task performance verified that the higher difficulty level leads to a higher cognitive load. Our behavioral data indicates a significant decrease in intensity estimates of food odors and non-food odors during the high compared to low cognitive load condition. We conclude that odor intensity estimation is influenced by real-life cognitive tasks which might in turn lead to overeating while distracted.
CRIS-Team WoS Importer:2021-08-06

Recent smell loss is the best predictor of COVID-19 among individuals with recent respiratory symptoms - Gerkin, Richard C.; Ohla, Kathrin; Veldhuizen, Maria G.; Joseph, Paule V.; Kelly, Christine E.; Bakke, Alyssa J.; Steele, Kimberley E.; Farruggia, Michael C.; Pellegrino, Robert; Pepino, Marta Y.; Bouysset, Cédric; Soler, Graciela M.; et al. (Chemical Senses, 2021)
In a preregistered, cross-sectional study, we investigated whether olfactory loss is a reliable predictor of COVID-19 using a crowdsourced questionnaire in 23 languages to assess symptoms in individuals self-reporting recent respiratory illness. We quantified changes in chemosensory abilities during the course of the respiratory illness using 0–100 visual analog scales (VAS) for participants reporting a positive (C19+; n = 4148) or negative (C19−; n = 546) COVID-19 laboratory test outcome. Logistic regression models identified univariate and multivariate predictors of COVID-19 status and post-COVID-19 olfactory recovery. Both C19+ and C19− groups exhibited smell loss, but it was significantly larger in C19+ participants (mean ± SD, C19+: −82.5 ± 27.2 points; C19−: −59.8 ± 37.7). Smell loss during illness was the best predictor of COVID-19 in both univariate and multivariate models (ROC AUC = 0.72). Additional variables provide negligible model improvement. VAS ratings of smell loss were more predictive than binary chemosensory yes/no-questions or other cardinal symptoms (e.g., fever). Olfactory recovery within 40 days of respiratory symptom onset was reported for 50% of participants and was best predicted by time since respiratory symptom onset. We find that quantified smell loss is the best predictor of COVID-19 amongst those with symptoms of respiratory illness. To aid clinicians and contact tracers in identifying individuals with a high likelihood of having COVID-19, we propose a novel 0–10 scale to screen for recent olfactory loss, the ODoR-19. We find that numeric ratings ≤2 indicate high odds of symptomatic COVID-19 (4 < OR < 10). Once independently validated, this tool could be deployed when viral lab tests are impractical or unavailable.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Anosmia; Chemosensory; Coronavirus; Hyposmia; Olfactory; Prediction

Reduction of olfactory sensitivity during normobaric hypoxia - Huppertz, Tilman; Freiherr, Jessica; Olzowy, Bernhard; Kisser, Ulrich; Stephan, Jutta; Fesl, Gunther; Haegler, Kathrin; Feddersen, Berend; Fischer, Rainald; Mees, Klaus; Becker, Sven (Auris Nasus Larynx, 2018)
Objective: Acute mountain sickness (AMS) is caused by a low partial pressure of oxygen and may occur above 2500 m. The aim of this research was to evaluate olfactory and gustatory abilities of healthy subjects during baseline conditions and after seven hours of normobaric hypoxia.Methods: Sixteen healthy subjects were assessed using the Sniffin' Sticks, as well as intensity and pleasantness ratings. Gustatory function was evaluated utilizing the Taste Strips. Experiments were carried out under baseline conditions (518 m altitude) followed by a second testing session after seven hours of normobaric hypoxia exposure (comparable to 4000 m altitude).Results: During normobaric hypoxia olfactory sensitivity and intensity estimates were significantly reduced.Conclusions: We conclude that normobaric hypoxia leads to a significant decrease of olfactory sensitivity and intensity ratings. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Normobaric hypoxia; Olfactory function; Smell; Taste

Seeing faces, when faces can't be seen: Wearing portrait photos has a positive effect on how patients perceive medical staff when face masks have to be worn - Wiesmann, Martin; Franz, Christiane; Sichtermann, Thorsten; Minkenberg, Jan; Mathern, Nathalie; Stockero, Andrea; Iordanishvili, Elene; Freiherr, Jessica; Hodson, Julian; Habel, Ute; Nikoubashman, Omid (PLoS ONE, 2021)
Introduction Since the onset of the coronavirus disease 2019 (COVID-19) pandemic, wearing surgical face masks has become mandatory for healthcare staff in many countries when interacting with patients. Recently, it has been shown that wearing face masks impairs social interaction by diminishing a person's ability to read the emotion of their counterparts, an essential prerequisite to respond adequately in social situations. It is easily conceivable that this may have a tangible negative influence on the communication and relationship between patients and healthcare personnel. We therefore investigated whether it has an effect on how patients perceive healthcare professionals when physicians and nursing staff wear portrait photos with their smiling faces in addition to face masks. Methods During the study period of 16 days, the medical staff of our Department wore surgical face masks at all times during any kind of interaction with patients. In a pseudorandomized order, all members of our staff additionally affixed their portrait photos to their work clothes on 8 of the 16 days. After completion of their visit, 226 patients were interviewed anonymously in a cross-sectional study design using a questionnaire in which they rated the following three items: Friendliness of staff, medical quality of treatment, and how well they felt taken care of during treatment in our Department. Results On days, on which staff wore photos, mean scores of the questionnaires were significantly higher than on non-photo days (p = 0.013; mean ± standard deviation = 92.8 ± 11.3 vs. 91.0 ± 12.6; median (range) = 97 (98) vs. 96 (76)). When analyzed separately, the increased scores were only significant for the item friendliness of staff (p = 0.009; mean ± standard deviation = 95.8 ± 6.3 vs. 92.2 ± 11.5; median (range) = 98 (39) vs. 97 (54)). Conclusion Our study suggests that the use of portrait photos with smiling faces has a positive effect on how patients perceive healthcare staff.
CRIS-Team Scopus Importer:2021-06-25

Semantic Congruence Alters Functional Connectivity during Olfactory-Visual Perception - Sijben, Rik; Hoffmann-Hensel, Sonja Maria; Rodriguez-Raecke, Rea; Haarmeier, Thomas; Freiherr, Jessica (Chemical Senses, 2018)
Previous research has shown that humans struggle to interpret multiple perceptual signals when the information provided by these signals is incongruent. In the context of olfactory-visual integration, behavioral and neuronal differences in response to congruent and incongruent stimulus pairs have been established. Here, we explored functional connectivity of the human brain with regard to the perception of congruent and incongruent food stimuli. Participants were simultaneously presented olfactory and visual stimuli of 4 different food objects, 2 healthy and 2 unhealthy objects. Stimulus pairs were grouped into "congruent" (olfactory and visual presentation of the same object), "semi-congruent" (stimuli of similar "healthiness"), and "incongruent" (healthy-unhealthy stimulus combination). Using functional magnetic resonance imaging and psychophysiological interaction (PPI) analyses, we revealed part of a neural network, the nodes of which show differential connectivity depending on the level of congruency of the presented stimulus combinations. This network relies strongly on, mostly left, inferior frontal gyrus. The analysis of such network transcends standard subtractive designs and indicates the need for more detailed formulations of neuronal models and increased specificity in functional imaging.
Keywords: crossmodal; fMRI; multisensory; olfaction; psychophysiological interaction (PPI); vision

Size of nostril opening as a measure of intranasal volume - Schriever, Valentin A.; Hummel, Thomas; Lundstrom, Johan N.; Freiherr, Jessica (Physiology & behavior, 2013)
The anatomy of the human intranasal cavity is complex and anatomical variations are known to affect olfactory functions. Measurement of anatomical variations via delineation of intranasal volume is, however, technically complicated as well as time-consuming. It is well documented that size of various body parts tends to correlate within the same individual. Therefore, in the current study, we explored the relationship between intranasal volume and the size of the flares, with the aim of using the area of the nostril opening as a potential predictor of intranasal volume. Structural whole-brain T1-weighted MR images of 69 healthy volunteers (35 women) were obtained using a 1.5 T standard clinical MRI scanner. The intranasal volume, as well as the area of the nostril opening, were delineated. Our results suggest that the intranasal volume is positively correlated with the area of the nostril. opening. Intranasal volume did not differ significantly between men and women although men had significant larger nostril openings. However, the correlation between intranasal volume and nostril opening was not influenced by the subject's gender. In conclusion, it is possible to obtain a good estimate of the intranasal volume using measurements of the nares. (c) 2012 Elsevier Inc. All rights reserved.
Keywords: Nasal anatomy; Nares; Nose; Airflow; Olfaction

Some like it, some do not: behavioral responses and central processing of olfactory-trigeminal mixture perception - Mueschenich, Franziska S.; Sichtermann, Thorsten; Di Francesco, Maria Elisa; Rodriguez-Raecke, Rea; Heim, Lennart; Singer, Marco; Wiesmann, Martin; Freiherr, Jessica (Brain Structure & Function, 2020)
Exploring the potential of eucalyptol as a masking agent for aversive odors, we found that eucalyptol masks the olfactory but not the trigeminal sensation of ammonia in a previous study. Here, we further investigate the processing of a mixture consisting of eucalyptol and ammonia, two olfactory-trigeminal stimuli. We presented the two pure odors and a mixture thereof to 33 healthy participants. The nostrils were stimulated alternately (monorhinal application). We analyzed the behavioral ratings (intensity and pleasantness) and functional brain images. First, we replicated our previous finding that, within the mixture, the eucalyptol component suppressed the olfactory intensity of the ammonia component. Second, mixture pleasantness was rated differently by participants depending on which component dominated their mixture perception. Approximately half of the volunteers rated the eucalyptol component as more intense and evaluated the mixture as pleasant (pleasant group). The other half rated the ammonia component as more intense and evaluated the mixture as unpleasant (unpleasant group). Third, these individual differences were also found in functional imaging data. Contrasting the mixture either to eucalyptol or to both single odors, neural activation was found in the unpleasant group only. Activation in the anterior insula and SII was interpreted as evidence for an attentional shift towards the potentially threatening mixture component ammonia and for trigeminal enhancement. In addition to insula and SII, further regions of the pain matrix were involved when assessing all participant responses to the mixture. Both a painful sensation and an attentional shift towards the unpleasant mixture component complicates the development of an efficient mask because a pleasant perception is an important requirement for malodor coverage.
CRIS-Team WoS Importer:2021-01-15

Statistical localization of human olfactory cortex - Seubert, Janina; Freiherr, Jessica; Djordjevic, Jelena; Lundstroem, Johan N. (NeuroImage, 2013)
Functional neuroimaging methods have been used extensively during the last decades to explore the neural substrates of olfactory processing. While a general consensus on the functional anatomy of olfactory cortex is beginning to emerge, the mechanisms behind the functions of individual processing nodes still remain debated. Further, it remains unclear to which extent divergent findings result from differences in methodological approaches. Using Activation Likelihood Estimation (ALE), the aim of the present study was to statistically combine all published data on functional neuroimaging of olfaction to provide a probability map reflecting the state of the field to date. Additionally, we grouped studies according to various methodological approaches to investigate whether these systematically affected the reported findings. A total of 45 studies (69 contrasts, 594 foci) met our inclusion criteria. Significant ALE peaks for odor against baseline were observed in areas commonly labeled as primary and secondary olfactory cortex, such as the piriform and orbitofrontal cortex, amygdala, anterior insula, and ventral putamen. In addition, differences were observed in the extent to which different methods were able to induce activation in these different nodes of the olfactory network. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Olfaction; Brain imaging; Activation likelihood estimation; Piriform cortex

Superadditive and Subadditive Neural Processing of Dynamic Auditory-Visual Objects in the Presence of Congruent Odors - Ohla, Kathrin; Hoechenberger, Richard; Freiherr, Jessica; Lundstrom, Johan N. (Chemical Senses, 2018)
Our sensory experiences comprise a variety of different inputs at any given time. Some of these experiences are unmistakable, others are ambiguous and profit from additional sensory information. Here, we explored whether the presence of a congruent odor influences the neural processing and sensory interaction of audio-visual objects using degraded videos (V) and sounds (A) of dynamic objects in unimodal and bimodal (AV) combinations without or with a congruent odor (VO, AO, AVO). Analyses of EEG data revealed superadditive and subadditive interaction effects. The topography and timing of these effects suggest evaluative rather than sensory processes as the underlying cause. Together, the results suggest that the mere presence of an odor affects the processing of A, V, and AV objects differently while multisensory interactions of AV and AVO objects have common neuronal mechanisms pointing to a robust, modality-independent network for the processing of redundant sensory information.
Keywords: auditory; context; EEG; multisensory interaction; olfactory; visual

Susceptibility-Weighted Angiography Visualizes Hypoxia in Cerebral Veins - Patzig, Maximilian; Feddersen, Berend; Haegler, Katrin; Olzowy, Bernhard; Mees, Klaus; Fischer, Rainald; Becker, Sven; Kisser, Ulrich; Freiherr, Jessica; Grashey, Rupert; Fesl, Gunther (Investigative Radiology, 2015)
Objectives: The objective of this study was to evaluate the influence of short-and long-term hypoxia on the depiction of cerebral veins in the susceptibility-weighted angiography (SWAN) sequence.Materials and Methods: In the context of a study on brain adaptation mechanisms to hypoxia, 16 healthy men (aged 20-28 years) were studied through magnetic resonance imaging (MRI) under room air conditions, short-term-hypoxia (7 minutes before and during the MRI scan), and long-term hypoxia (8.5 hours before and during the MRI scan). Oxygen saturation was continuously measured using a finger-mounted pulse oximeter. Two independent blinded readers compared the 3 scans of each participant and graded the SWAN source images and minimum intensity projections according to the size, number, and signal intensity of the cerebral veins. Signal intensities of deep cerebral veins were measured, and signal intensity proportions of deep cerebral veins to different parenchymal brain regions were calculated.Results: Nine subjects could be included in the study. In all of them, both readers correctly distinguished the 2 hypoxia scans from the baseline scan, grading the SWAN images acquired under hypoxic conditions as visualizing cerebral veins more prominently. Signal intensities of the deep cerebral veins and signal intensity proportions were significantly lower in the hypoxia scans. No significant differences between short-term and long-term hypoxia were found on visual inspections and signal intensity measurements. This correlated with the results of the pulse oximetry: mean O-2 saturation values were 97.9% +/- 1.2% (baseline), 84.1% +/- 3.8% (short-term hypoxia), and 82.8% +/- 4.4% (long-term hypoxia), respectively.Conclusions: Hypoxia leads to visible and measurable changes in cerebral veins as depicted through SWAN. Possible clinical implications of this finding include stroke and tumor imaging and need further investigation.
Keywords: hypoxia; MRI; SWAN

Targeting the brain through the nose. Effects of intranasally administered insulin - Bruenner, Y. F.; Benedict, Christian; Freiherr, Jessica (Der Nervenarzt, 2013)
The assumption that the human brain is an insulin-independent organ was disproved with the discovery of insulin receptors in the central nervous system in the year 1978. Evidence has been provided for a high density of insulin receptors in brain regions responsible for cognitive memory processes (hippocampus) and for the regulation of appetite (hypothalamus). Accordingly, in animal studies an increased insulin level in the central nervous system leads to an improvement of hippocampal memory function and a decrease of food intake. Similar results were obtained in humans using the method of intranasal administration of insulin. Intranasal insulin reaches the brain and the cerebrospinal fluid via the olfactory epithelium and olfactory nerve fiber bundles leading through the lamina cribrosa to the olfactory bulb. Thus, this method renders the investigation of specific insulin effects in humans possible. The therapeutic potential of an intranasal insulin administration for the treatment of diseases for which an imbalance of the central nervous insulin metabolism is discussed (e.g. Alzheimer's disease, diabetes mellitus and obesity) can only be estimated with the help of further clinical studies.
Keywords: Cerebral insulin level; Declarative memory; Food intake; Thermogenesis; Intranasal application

The 40-item Monell Extended Sniffin' Sticks Identification Test (MONEX-40) - Freiherr, Jessica; Gordon, Amy R.; Alden, Eva C.; Ponting, Andrea L.; Hernandez, Monica F.; Boesveldt, Sanne; Lundstrom, Johan N. (Journal of Neuroscience Methods, 2012)
Background: Most existing olfactory identification (ID) tests have the primary aim of diagnosing clinical olfactory dysfunction, thereby rendering them sub-optimal for experimental settings where the aim is to detect differences in healthy subjects' odor ID abilities.Materials and methods: We have developed an extended version of the olfactory ID subtest of the Sniffin' Sticks test battery to better assess the variability in ID scores and thereby olfactory abilities of healthy, adult individuals. Twenty-four odorants, corresponding cue labels, and distractor labels were added to the existing 16-item Sniffin' Sticks ID test to create the 40-item Monell Extended Sniffin' Sticks Identification Test (MONEX-40). The MONEX-40 was administered to 259 healthy young subjects, of which 72 were retested on an average of 212 days (SD 112 days) later.Results: The added odor items demonstrated good validity, as shown by a significant correlation of the results with the original 16-item ID test. In addition, the MONEX-40 achieved a significant test-retest and split-half reliability.Conclusions: Taken together, these results suggest that the MONEX-40 is a reliable method for experimental assessment of odor ID ability in healthy, young individuals. Moreover, its use of a wider range of odors allows the experimenter to present subsets of the MONEX-40 within the same experiment while maintaining statistical power. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Smell; Olfaction; Reliability; Validity

The hedonics of olfactory induced memories - a new model for the analyses of emotional blunting - Thürauf, Norbert; Sollmann, Manuel; Fuchs, Michael; Jäger, Jakob; Mettang, Melissa; Reich, Karin; Kornhuber, Johannes; Sperling, Wolgang; Freiherr, Jessica (CHEMICAL SENSES, 2020)
CRIS-Team WoS Importer:2020-06-23

The human body odor compound androstadienone increases neural conflict coupled to higher behavioral costs during an emotional Stroop task - Hornung, Jonas; Kogler, Lydia; Erb, Michael; Freiherr, Jessica; Derntl, Birgit (NeuroImage, 2018)
The androgen derivative androstadienone (AND) is a substance found in human sweat and thus may act as human chemosignal. With the current experiment, we aimed to explore in which way AND affects interference processing during an emotional Stroop task which used human faces as target and emotional words as distractor stimuli. This was complemented by functional magnetic resonance imaging (fMRI) to unravel the neural mechanism of AND-action. Based on previous accounts we expected AND to increase neural activation in areas commonly implicated in evaluation of emotional face processing and to change neural activation in brain regions linked to interference processing.For this aim, a total of 80 healthy individuals (oral contraceptive users, luteal women, men) were tested twice on two consecutive days with an emotional Stroop task using fMRI.Our results suggest that AND increases interference processing in brain areas that are heavily recruited during emotional conflict. At the same time, correlation analyses revealed that this neural interference processing was paralleled by higher behavioral costs (response times) with higher interference related brain activation under AND. Furthermore, AND elicited higher activation in regions implicated in emotional face processing including right fusiform gyrus, inferior frontal gyrus and dorsomedial cortex. In this connection, neural activation was not coupled to behavioral outcome. Furthermore, despite previous accounts of increased hypothalamic activation under AND, we were not able to replicate this finding and discuss possible reasons for this discrepancy.To conclude, AND increased interference processing in regions heavily recruited during emotional conflict which was coupled to higher costs in resolving emotional conflicts with stronger interference-related brain activation under AND. At the moment it remains unclear whether these effects are due to changes in conflict detection or resolution. However, evidence most consistently suggests that AND does not draw attention to the most potent socio-emotional information (human faces) but rather highlights representations of emotional words.
Keywords: Emotional Stroop task; Androstadienone; Emotional conflict; Emotional faces; fMRI

The human body odor compound androstadienone leads to anger-dependent effects in an emotional Stroop but not dot-probe task using human faces - Hornung, Jonas; Kogler, Lydia; Wolpert, Stephan; Freiherr, Jessica; Derntl, Birgit (PLoS ONE, 2017)
The androgen derivative androstadienone is a substance found in human sweat and thus is a putative human chemosignal. Androstadienone has been studied with respect to effects on mood states, attractiveness ratings, physiological and neural activation. With the current experiment, we aimed to explore in which way androstadienone affects attention to social cues (human faces). Moreover, we wanted to test whether effects depend on specific emotions, the participants' sex and individual sensitivity to smell androstadienone. To do so, we investigated 56 healthy individuals (thereof 29 females taking oral contraceptives) with two attention tasks on two consecutive days (once under androstadienone, once under placebo exposure in pseudorandomized order). With an emotional dot-probe task we measured visuo-spatial cueing while an emotional Stroop task allowed us to investigate interference control. Our results suggest that androstadienone acts in a sex, task and emotion-specific manner as a reduction in interference processes in the emotional Stroop task was only apparent for angry faces in men under androstadienone exposure. More specifically, men showed a smaller difference in reaction times for congruent compared to incongruent trials. At the same time also women were slightly affected by smelling androstadienone as they classified angry faces more often correctly under androstadienone. For the emotional dot-probe task no modulation by androstadienone was observed. Furthermore, in both attention paradigms individual sensitivity to androstadienone was neither correlated with reaction times nor error rates in men and women. To conclude, exposure to androstadienone seems to potentiate the relevance of angry faces in both men and women in connection with interference control, while processes of visuo-spatial cueing remain unaffected.

The impact of cognitive distraction on gustatory perception in volunteers with obesity - Ruda, Iryna; Chellapandian, Deepak Charles; Freiherr, Jessica (Scientific Reports, 2024)
Obesity, a global health challenge, is influenced by biological, behavioral, socioeconomical, and environmental factors. In our technology-driven world, distracted eating is prevalent, yet neurocognitive mechanisms behind it remain poorly understood. This study targets individuals with overweight and obesity, exploring taste perception under distraction comprehensively. Participants formed two distinct groups based on their Body Mass Index (BMI), lean and overweight/obese. During the experiment participants received gustatory stimuli while playing a Tetris game of various difficulty levels. Participants rated taste intensity and pleasantness, with linear mixed models analyzing distraction effects. Results confirmed that high distraction levels reduced perception of taste intensity (p = 0.017) and taste pleasantness (p = 0.022), with variations influenced by gender and weight status. Individuals in the overweight/obese group exhibited most profound intensity changes during distraction (p = 0.01). Taste sensitivity ratings positively correlated with BMI interacting with gender (male r = 0.227, p < 0.001; female r = 0.101, p < 0.001). Overall across both groups, female participants demonstrated higher taste sensitivity compared to male participants (p < 0.001). This study highlights the impact of cognitive distraction during consumption on taste perception, particularly in relation to weight status and gender, underscoring their significant roles in this interplay.
CRIS-Team Scopus Importer:2024-06-28
Keywords: Distracted eating; Gustatory perception; Intensity; Obesity; Pleasantness

The influence of androstadienone during psychosocial stress is modulated by gender, trait anxiety and subjective stress: An fMRI study - Chung, K. C.; Springer, I.; Kogler, L.; Turetsky, B.; Freiherr, Jessica; Derntl, B. (Psychoneuroendocrinology, 2016)
Androstadienone (ANDR), a bodily secreted steroid compound, is a socially relevant chemosignal that modulates subjective and (neuro)physiological responses, predominantly in females. The impact of ANDR on stress responses in males and females has not been explored. Therefore, this fMRI study aimed to examine psychosocial stress reactions induced by mental arithmetic and social evaluation on behavioral and hormonal levels (46 participants: 15 naturally cycling females in their early follicular phase (EF), 15 females on hormonal contraceptives (HC) and 16 males); and on a neural level (40 participants: 13 EF-females, 13 HC-females and 14 males) in an ANDR and placebo treatment repeated-measures design.While no gender differences emerged in subjective ratings and performance during stress, neural activation patterns differed significantly. Besides, ANDR attenuated the post-stress increase of negative mood in all participants. Region of interest analyses showed that irrespective of treatment, males showed stronger activation of the dorsolateral prefrontal cortex (DLPFC) than females. At the whole brain level, gender differences emerged indicating stronger fronto-parietal activation in males compared to HC-females on both treatments. Males showed stronger visual and fusiform activation than EF-females under ANDR. Both female groups did not show stronger activation than males. Further, error ratio in the ANDR-stress condition was positively associated with their post-stress cortisol level and increase in subjective stress in males; and male DLPFC activity in the ANDR-stress condition was negatively associated with trait anxiety. Surprisingly, compared to HC-females, EF-female only showed stronger activation of arousal-related areas under placebo treatment.Taken together, these findings suggest that the male stress reaction under social evaluative threat was stronger than female stress reactions as a function of ANDR. More specifically, this effect on behavioral and neural stress reactions seems to depend on trait anxiety in males only. The study highlights the significance of a chemosignal in enhancing social threat that may facilitate adaptive stress responses. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Androstadienone; Social threat; Gender; Dorsolateral prefrontal cortex; Trait-anxiety

The influence of androstadienone during psychosocial stress is modulated by gender, trait anxiety and subjective stress: An fMRI study (vol 68, pg 126, 2016) - Chung, K. C.; Springer, I.; Kogler, L.; Turetsky, B.; Freiherr, Jessica; Derntl, B. (Psychoneuroendocrinology, 2016)

The influence of androstadienone on neural stress reactions in depression - Chung, Ka Chun; Turetsky, Bruce; Freiherr, Jessica; Derntl, Birgit (Chemical Senses, 2016)

The Influence of Menstrual Cycle and Androstadienone on Female Stress Reactions: An fMRI Study - Chung, Ka Chun; Peisen, Felix; Kogler, Lydia; Radke, Sina; Turetsky, Bruce; Freiherr, Jessica; Derntl, Birgit (Frontiers in Human Neuroscience, 2016)
Communicating threats and stress via biological signaling is common in animals. In humans, androstadienone (ANDR), a synthetic male steroid, is a socially relevant chemosignal exhibited to increase positive mood and cortisol levels specifically in (periovulatory) females in positively arousing contexts. In a negative context, we expected that such effects of ANDR could amplify social evaluative threat depending on the stress sensitivity, which differs between menstrual cycle phases. Therefore, this fMRI study aimed to examine psychosocial stress reactions on behavioral, hormonal and neural levels in 31 naturally cycling females, between 15 early follicular (EF) and 16 mid-luteal (ML) females tested with ANDR and placebo treatment in a repeated measures design. Regardless of odor stimulation, psychosocial stress (i.e., mental arithmetic task with social evaluative threat) led to elevated negative mood and anxiety in all females. A negative association of social threat related amygdala activation and competence ratings appeared in ML-females, indicating enhanced threat processing by ANDR, particularly in ML-females who felt less competent early in the stress experience. Further, ML-females showed reduced performance and stronger stress related hippocampus activation compared to EF-females under ANDR. Hippocampal activation in ML-females also correlated positively with post-stress subjective stress. Contrarily, such patterns were not observed in EF-females or under placebo in either group. Strikingly, unlike passive emotional processing, ANDR in a stressful context decreased cortisol concentration in all females. This points to a more complex interaction of ovarian/gonadal hormones in social threat processing and stress reactivity. Our findings suggest that ANDR enhanced initial evaluation of self-related social threat in ML-females. Female stress reactions are related to stress sensitivity through enhanced awareness and processing of social cues in a stressful context, with menstrual cycle phase being a critical factor.
Keywords: menstrual cycle; stress; social threat; cortisol; hippocampus; amygdala

The Influence of Menstrual Cycle and Androstadienone on Female Stress Reactions: An fMRI Study (vol 10, 44, 2016) - Chung, Ka Chun; Peisen, Felix; Kogler, Lydia; Radke, Sina; Turetsky, Bruce; Freiherr, Jessica; Derntl, Birgit (Frontiers in Human Neuroscience, 2016)
Keywords: menstrual cycle; stress; social threat; cortisol; hippocampus; amygdala

The role of odor context cues in episodic memory processing - Reichert, Johanna; Ninaus, Manuel; Schuehly, Wolfgang; Hirschmann, Christina; Bagga, Deepika; Freiherr, Jessica; Schoepf, Veronika (Chemical Senses, 2018)

The Scent of the Other Woman: Impact of Female Body Odor during Intrasexual Competition - Freiherr, Jessica; Mutic, Smiljana; Cavazzana, Annachiara; Rocha, Marta; Soares, Sandra; Lundstrom, Johan; Parma, Valentina (Chemical Senses, 2016)

The scent of the other women: Body odor-induced behavioral and physiological effects on face categorization - Mutic, Smiljana; Freiherr, Jessica; Cavazzana, Annachiara; Rocha, Marta; Soares, Sandra C.; Parma, Valentina (Physiology & behavior, 2019)
In body odor research, the interaction of female donors and receivers is scarcely investigated. With the aim to investigate effects of female body odor in a competitive context, we tested 51 women divided into two groups (i.e., a competitive and a non-competitive group, based on verbal instructions). Between groups, we explored whether female body odor exposure (vs. masker odor) modulates emotion categorization (via RT variance and distribution) and physiological reactions (via instantaneous heart rate) in a task with dynamic male and female faces as either angry or happy. Women in the competitive group reported to feel more competitive and performed more accurately. They gathered more emotional information to categorize dynamic faces and when additionally exposed to female body odor, they showed a resistance to cardiac deceleration. Lapses of attention (via RT distribution) occurred irrespective of body odor exposure. Our results support the idea that female body odors, presented in a competitive context, contrast cardiac deceleration and, by tendency, modulate emotion categorization. Data are discussed in the context of chemosignaling and social interactions among women.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Chemosensation; Chemosignal; Heart rate; Intrasexual competition; Olfaction; Smell

Trigeminal Stimulus Menthol Masks Bitter Off-Flavor of Artificial Sweetener Acesulfame-K - Buechner, Kai; Haagen, Jana; Sastrosubroto, Ashtri; Kerpes, Roland; Freiherr, Jessica; Becker, Thomas (Foods, 2022)
Consumer health concerns and regulatory policies lead to a growing demand for sugar-sweetened beverage alternatives. A reduced energy content can be achieved using artificial sweeteners, which often also convey a metallic or bitter off-flavor. Therefore, the alteration of sweetness perception and masking of potential off-flavors are paramount for improving sweet beverages. Trigeminal stimuli, such as capsaicin (spicy) or menthol (cooling), have been used to influence taste perception in food items, although their use in beverages has not yet been systematically investigated. Here, the influence of menthol on sweetness perception in an aqueous solution is examined both on the sensory and psychophysiological level. The addition of menthol had no sensory effect on sweetness perception; however, psychophysiological measurements suggest a boost in the physiological response to cold perception through the addition of sugar. Moreover, menthol addition shifted the recognition threshold of unpleasant bitterness of the sweetener acesulfame-K from 21.35 to 36.93 mg/L, masking the off-flavor. These findings illuminate the complexity of trigeminal perception influences on taste. Further investigation of these effects can render trigeminal stimuli an effective tool to enhance beverage aroma and flavor.
CRIS-Team Scopus Importer:2022-10-07
Keywords: artificial sweetener; menthol; nervus trigeminus; off-flavor; psychophysiology

Trimodal processing of complex stimuli in inferior parietal cortex is modality-independent - Porada, Danja K.; Regenbogen, Christina; Freiherr, Jessica; Seubert, Janina; Lundström, Johan N. (Cortex, 2021)
In humans, multisensory mechanisms facilitate object processing through integration of sensory signals that match in their temporal and spatial occurrence as well as their meaning. The generalizability of such integration processes across different sensory modalities is, however, to date not well understood. As such, it remains unknown whether there are cerebral areas that process object-related signals independently of the specific senses from which they arise, and whether these areas show different response profiles depending on the number of sensory channels that carry information. To address these questions, we presented participants with dynamic stimuli that simultaneously emitted object-related sensory information via one, two, or three channels (sight, sound, smell) in the MR scanner. By comparing neural activation patterns between various integration processes differing in type and number of stimulated senses, we showed that the left inferior frontal gyrus and areas within the left inferior parietal cortex were engaged independently of the number and type of sensory input streams. Activation in these areas was enhanced during bimodal stimulation, compared to the sum of unimodal activations, and increased even further during trimodal stimulation. Taken together, our findings demonstrate that activation of the inferior parietal cortex during processing and integration of meaningful multisensory stimuli is both modality-independent and modulated by the number of available sensory modalities. This suggests that the processing demand placed on the parietal cortex increases with the number of sensory input streams carrying meaningful information, likely due to the increasing complexity of such stimuli.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Auditory-visual-olfactory; Inferior parietal cortex; Intraparietal sulcus; Multisensory integration; Object information; Trimodal

You Smell Dangerous: Communicating Fight Responses Through Human Chemosignals of Aggression - Mutic, Smiljana; Parma, Valentina; Bruenner, Yvonne F.; Freiherr, Jessica (Chemical Senses, 2016)
The ability to detect conspecifics that represent a potential harm for an individual represents a high survival benefit. Humans communicate socially relevant information using all sensory modalities, including the chemosensory systems. In study 1, we investigated whether the body odor of a stranger with the intention to harm serves as a chemosignal of aggression. Sixteen healthy male participants donated their body odor while engaging in a boxing session characterized by aggression-induction methods (chemosignal of aggression) and while performing an ergometer session (exercise chemosignal). Self-reports on aggression-related physical activity, motivation to harm and angry emotions selectively increased after aggression induction. In study 2, we examined whether receivers smelling such chemosignals experience emotional contagion (e.g., anger) or emotional reciprocity (e.g., anxiety). The aggression and exercise chemosignals were therefore presented to 22 healthy normosmic participants in a double-blind, randomized exposure during which affective/cognitive processing was examined (i.e., emotion recognition task, emotional stroop task). Behavioral results indicate that chemosignals of aggression induce an affective/cognitive modulation compatible with an anxiety reaction in the recipients. These findings are discussed in light of mechanisms of emotional reciprocity as a way to convey not only affective but also motivational information via chemosensory signals in humans.
Keywords: approach motivation; olfaction; social chemosignals; threat